Laminated film
By using a resin layer containing an antistatic agent in the manufacturing process of electronic components, the problem of depression and antistatic dependence on humidity caused by the silicone compound is solved, and the light peeling and antistatic properties of the surface layer are achieved, and the performance of electronic components and batteries is improved.
Patent Information
- Application Number
- CN202380062223.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-05
- Filing Date
- 2023-06-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-06-26
AI Technical Summary
The release film used in the prior art in the manufacturing process of electronic components has problems with depressions or pinholes caused by silicone compounds, and the antistatic property depends on humidity, resulting in insufficient resistance value.
A resin layer containing an antistatic agent is applied on the thermoplastic resin substrate film, and the density and antistatic properties of the resin layer are ensured by adjusting the ratio of nitrogen element to carbon element and the surface resistivity value.
The surface layer is light peeling and excellent antistatic properties, avoiding contamination caused by silicone and falling off of antistatic agents, and improving the performance of electronic components and batteries.
Smart Images

Figure BDA0005287102380000281 
Figure BDA0005287102380000291 
Figure BDA0005287102380000301
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated film having a resin layer on at least one surface of a base film. Background Art
[0002] Plastic films are widely used as substrate films in many applications such as magnetic recording materials and packaging materials due to their excellent mechanical properties, electrical properties, dimensional stability, transparency, and chemical resistance. These plastic films are generally used in the form of laminated films in which a functional resin layer is applied to the surface by coating the surface with a coating and curing the coating.
[0003] In particular, when used as a process film used in the manufacture of electronic components, a coating agent such as a ceramic slurry is applied to the resin layer of the polyester film (hereinafter referred to as the surface layer), and after drying, the surface layer is peeled off from the polyester film. In the process of peeling off the surface layer, a film with excellent demoulding properties is required from the viewpoint of processability, and a film in which an organosilicon compound and an amino resin are contained in the resin layer is generally used (Patent Document 1). However, when these organosilicon compounds are contained in the resin layer, the surface free energy of the resin layer becomes low, so sometimes the coating properties of the coating agent such as the ceramic slurry become poor.
[0004] In recent years, with the miniaturization and high performance of electronic devices, high-quality release films with less foreign matter and defects are required, and research has been conducted to suppress the adhesion of foreign matter and peeling static electricity by adding antistatic materials to release films, for example (Patent Document 2).
[0005] On the other hand, as a release agent (hereinafter, described as non-organosilicon release agent) that is excellent in the coating property of a coating agent such as a ceramic slurry, a resin containing a long-chain alkyl group, an olefin resin, a fluorine compound, a wax compound, especially a resin containing a long-chain alkyl group, and an amino resin and an antistatic agent that can form a dense cross-linked film have been studied (patent document 3). Further, a release film having a stable antistatic function and excellent stripping function by using a carbon-based antistatic agent such as carbon nanofiber has also been studied (patent document 4). In addition, in order to solve the problem of poor compatibility between a polythiophene-based antistatic agent and an organosilicon-based release agent, a release layer is provided on the antistatic layer or on another face after an antistatic layer is provided on the substrate film (patent document 5). Further, in order to obtain a release film having excellent releasability without stripping charge, a release layer is provided on one side of a polyester film and a release film having an antistatic layer is provided on the other face (patent document 6). On the other hand, Patent Document 7 proposes an antistatic film having a conductive layer containing carbon nanotubes (A), a carbon nanotube dispersant (B), a binder resin (C) and an acrylic resin (D) having an alkyl chain with more than 12 carbon atoms, provided on at least one side of a thermoplastic resin film as a film having antistatic properties and antifouling properties that allow an attached adhesive layer to be easily wiped off.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2017-105092
[0009] Patent Document 2: Japanese Patent Application Publication No. 2020-023690
[0010] Patent Document 3: Japanese Patent Application Publication No. 2019-131826
[0011] Patent Document 4: Japanese Patent Application Publication No. 2007-190717
[0012] Patent Document 5: International Publication No. 2016 / 133092
[0013] Patent Document 6: Japanese Patent Application Publication No. 2000-158611
[0014] Patent Document 7: Japanese Patent Application Publication No. 2010-072423 Summary of the invention
[0015] Problems to be solved by the invention
[0016] The inventors of the present invention have studied the above-mentioned technology and found that when the formulations of Patent Documents 1 and 2 using an organosilicon compound as a mold release agent are used as a process film used in the manufacture of electronic components, the process of applying a surface layer such as a ceramic slurry on the resin layer of a polyester film, drying it, and then peeling the dried surface layer from the polyester film may cause problems such as depressions or pinholes caused by the organosilicon compound. In addition, it was found that even if there is no major problem in coating, the organosilicon compound may move to the surface layer side when peeling the surface layer from the polyester film, and residues may remain on the surface after the ceramic slurry is fired, thereby adversely affecting the performance of the electronic component.
[0017] The formulation of Patent Document 3, which avoids contamination caused by silicone compounds by using a non-silicone release agent, has antistatic properties that depend on humidity, etc., and cannot obtain a sufficient resistance value. Furthermore, when an electron conductive antistatic agent that is not affected by humidity is used in combination with an amino resin, it is confirmed that the antistatic properties deteriorate, with an insufficient resistance value.
[0018] Regarding the formulation of Patent Document 4 using carbon nanofibers as an antistatic material, although good antistatic properties are obtained, the crosslinking property of the resin layer is not sufficiently high, so the peeling force of the surface layer such as ceramic slurry becomes high. Therefore, in the process of peeling the surface layer from the polyester film, the surface layer is sometimes broken, and further, the carbon nanofibers fall off and are transferred to the surface layer side, which sometimes has an adverse effect on the performance of the electronic component.
[0019] Patent document 5, in which a release layer is provided on the antistatic layer or on another surface after an antistatic layer is provided on a substrate film, has problems in productivity and cost due to the need for multiple coating / drying processes. In addition, the prescription of patent document 6, in which a release layer is provided on one surface of a polyester film and an antistatic layer is provided on the other surface, sometimes fails to obtain a sufficient charge suppression effect when the ceramic slurry is peeled off. Further, the inventors of the present invention and others have studied the technology described in patent document 7, and as a result, for the "antifouling property of easily wiping off the attached adhesive layer", in the method of use of peeling the surface layer from the polyester film as the target of the present application, it is sometimes difficult to peel off the surface layer.
[0020] In addition, in recent years, although research has been conducted on the use of release films in the vapor deposition process in the manufacture of lithium-ion batteries and the coating and transfer process of electrolytes and electrodes in the manufacture of all-solid-state batteries, the release layer is required to have heat resistance, solvent resistance, and antistatic properties in harsh environments such as vacuum and absolute dry conditions.
[0021] Therefore, in the present invention, the object is to provide a laminated film having excellent peelability and antistatic properties of the surface layer, and further having no contamination caused by silicone and no fall-off of antistatic materials, which can help improve the performance of electronic components and batteries. In addition, the laminated film of the present invention is also excellent in productivity and cost because the resin composition containing a release agent and an antistatic agent is processed in a continuous coating / drying process.
[0022] Means for solving problems
[0023] In order to solve the above-mentioned problems, the present invention includes the following configurations.
[0024] [1] A laminated film comprising a thermoplastic resin base film and a resin layer X containing an antistatic agent on at least one surface thereof, the laminated film satisfying all of the following conditions (1) to (3).
[0025] (1) The average content ratio of nitrogen atoms to carbon atoms per 1 nm of the resin layer X calculated from the ratio of nitrogen to carbon elements (N / C) and the thickness (nm) of the resin layer X is 0.0030 [nm -1 ] The above ratio of nitrogen element to carbon element is calculated by high-resolution Rutherford backscattering method (HR-RBS method).
[0026] (2) The surface resistivity of the resin layer X is 1.0×10 10 Ω / □ or less.
[0027] (3) The surface free energy of the resin layer X is 20.0 mN / m or more and less than 30.0 mN / m.
[0028] [2] A laminated film comprising a resin layer X containing an antistatic agent on at least one surface of a thermoplastic resin base film, wherein the resin layer X contains a long-chain alkyl resin, a melamine compound and an acrylic resin.
[0029] [3] The laminated film according to [1] or [2], wherein the antistatic agent contained in the resin layer X is a conductive carbon material.
[0030] [4] The laminated film according to [3], wherein the antistatic agent contained in the resin layer X is carbon nanotubes.
[0031] [5] According to any one of [1] to [4], when the surface of the above-mentioned resin layer X is analyzed by time-of-flight secondary ion mass spectrometry, the ratio (P / K) [-] of the peak intensity (P) of the fragment derived from polydimethylsiloxane to the peak intensity (K) of the fragment detected with maximum intensity is less than 0.01.
[0032] [6] The laminated film according to any one of [1] to [5], wherein the resin layer X contains a long-chain alkyl resin as a release agent, and the long-chain alkyl resin has an exothermic peak temperature (Tc) of 30°C to 90°C when the temperature is increased from 25°C to 200°C at 20°C / min and then decreased from 200°C to -50°C at 20°C / min using a differential scanning calorimeter (DSC).
[0033] [7] The laminated film according to [6], wherein the resin layer X contains a long-chain alkyl resin and a melamine compound, and contains at least one resin selected from acrylic resins, polyester resins, epoxy resins and urethane resins.
[0034] [8] According to the laminated film described in [1] to [7], with respect to the X-ray absorption near-edge structure (XANES) spectrum of the K absorption edge of carbon in the X-ray absorption fine structure (XAFS) spectrum of the above-mentioned resin layer X measured by the partial electron yield method, when the angle between the incident X-ray and the plane of the above-mentioned resin layer X is set to θ and the spectrum intensity of 293.5 eV is set to I(θ), I(15°)-I(90°)≥0.10 is satisfied.
[0035] [9] The laminated film according to any one of [2] and [5] to [8], wherein the long-chain alkyl resin is a block copolymer.
[0036]
[10] The laminated film according to any one of [1] to [9], wherein the thermoplastic resin substrate film is a polyester film containing at least one of a biomass raw material and a recycled raw material.
[0037]
[11] The laminated film according to [1] to
[10] , comprising a resin layer Y on the surface opposite to the resin layer X, and having a surface resistivity of 1.0×10 10 Ω / □ or less.
[0038]
[12] The laminated film according to
[11] , wherein the resin layer Y contains carbon nanotubes.
[0039]
[13] The laminated film according to any one of [1] to
[12] , which is used in a manufacturing process of an electronic component or a battery component.
[0040] Effects of the Invention
[0041] According to the present invention, by providing a releasable laminate film which has both light peelability and antistatic properties of the resin layer provided in the laminate film, thereby achieving good processability in the process of peeling off the surface layer, and having no contamination caused by silicone and no detachment of the antistatic agent, the performance of electronic components and batteries can be improved. DETAILED DESCRIPTION
[0042] As the first aspect of the laminated film of the present invention, the resin layer X containing an antistatic agent needs to satisfy all of the following requirements (1) to (3).
[0043] Regarding the first aspect, first, the meaning of each characteristic and an example of a control method will be described.
[0044] (1) The average content ratio of nitrogen atoms to carbon atoms per 1 nm of the resin layer X calculated from the ratio of nitrogen to carbon elements (N / C) and the thickness (nm) of the resin layer X is 0.0030 [nm -1 ] The above ratio of nitrogen element to carbon element is calculated by high-resolution Rutherford backscattering method (HR-RBS method).
[0045] (2) The surface resistivity of the resin layer X is 1.0×10 10 Ω / □ or less.
[0046] (3) The surface free energy of the resin layer X is 20.0 mN / m or more and less than 30.0 mN / m.
[0047] As a first requirement of the resin layer X included in the laminated film of the present invention, it is necessary that the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X calculated from the ratio of nitrogen atoms to carbon atoms (N / C) and the thickness (nm) of the resin layer X is 0.0030 [nm -1 ] The above ratio of nitrogen atoms to carbon atoms is calculated by high-resolution Rutherford backscattering method (HR-RBS method).
[0048] Here, the atomic weight calculated by the high-resolution Rutherford backscattering method (HR-RBS method) is described. For laminated films, there are a large number of methods for quantifying the bonding state and hardness of the resin layer surface. For example, methods such as vibration spectroscopy using infrared spectroscopy and indentation hardness analysis using nanoindentation can be cited, but these methods are difficult to separate from the polyester film part equivalent to the substrate, and it is difficult to suppress the influence of the polyester film part and grasp the characteristics of the resin layer more accurately, but the characteristics of the resin layer can be grasped more accurately by using the HR-RBS method. In the case where the measured sample is a laminated film having a resin layer on one side of the polyester film, the HR-RBS method is a method for obtaining surface structural information by incident He ions from the surface direction of the resin layer of the measured sample along the direction of the substrate layer, and analyzing the energy of the He ions scattered from the back side, that is, the substrate layer direction, along the substrate layer surface direction. By using this method, element information, depth information, and concentration information on the surface of the resin layer can be obtained. Since this method is a surface-sensitive analysis method, it can be effective and highly accurately analyzed for the characteristics of a layer formed on the surface such as a resin layer.
[0049] The information that can be obtained by the HR-RBS method is specifically the ion intensity (i.e., the number) of ions scattered with a specific energy. Energy is equivalent to element information, and ion intensity is equivalent to the amount of each element. Since the ion intensity is a value that varies according to the measurement conditions, it is actually converted into the relative amount of the element of interest.
[0050] As a numerical value for characterizing the surface characteristics of a resin layer composed of a non-silicone material, the inventors and others have conducted research and found that by controlling the average content ratio of nitrogen atoms and carbon atoms per 1nm thickness of the resin layer X calculated by the ratio of nitrogen atoms to carbon atoms (N / C) and the thickness (nm) of the resin layer X to a preferred range, the fall-off of the antistatic agent can be suppressed in the resin layer using a non-silicone release agent. Nitrogen atoms exist in large quantities at the reaction site of organic compounds, so it can be considered as an indicator that effectively characterizes the physical properties of the film. On the other hand, the absolute number of each element also increases or decreases according to the thickness of the resin layer, so in order to more accurately represent the characteristics of the resin layer, it is necessary to convert it into a numerical value per unit thickness.
[0051] The average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X calculated by the ratio of nitrogen atoms to carbon atoms (N / C) and the thickness (nm) of the resin layer X was 0.0030 [nm -1 ] or more, thereby improving the cross-linking density of the resin layer X, and inhibiting the adhesive component contained in the slurry from penetrating into the interior of the resin layer X when applying a coating agent such as a ceramic slurry, so that the surface layer can be peeled off easily. Furthermore, since the antistatic agent is retained in the resin layer X, the fall of the antistatic agent can be inhibited.
[0052] The average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X is less than 0.0030 [nm -1 ], sometimes, for example, when the surface layer is peeled off, the mold release is insufficient, or the antistatic agent falls off from the resin layer X. From the above viewpoints, in the laminated film of the present invention, the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X is preferably 0.0050 [nm -1 ] or more, more preferably 0.0080[nm -1 On the other hand, there is no particular upper limit on the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X. When the resin layer X is composed of an organic compound, the upper limit is about 0.1000 [nm -1 ] is the actual upper limit, and is preferably 0.0200[nm -1]. It should be noted that the details of the measurement of the ratio of nitrogen atoms to carbon atoms (N / C) by the HR-RBS method will be described later.
[0053] In the laminated film of the present invention, the ratio of nitrogen atoms to carbon atoms (N / C) calculated by the HR-RBS method and the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X can be controlled not only by adjusting the amount of components constituting the resin layer X, but also by adjusting the crosslinking state of the resin layer X, adjusting the film density by drying when the resin layer X is formed by a wet coating method, and performing an in-line coating method in the polyester film manufacturing process to coat the resin layer X. The preferred composition of the resin layer X constituting the laminated film of the present invention and the preferred method for producing the laminated film will be described later.
[0054] As a second requirement of the resin layer X included in the laminated film of the present invention, it is necessary that the surface resistivity value satisfies 1.0×10 10 Ω / □ or less. If the surface resistivity is 1.0×10 10 Ω / □ or less, the adhesion of foreign matter and the peeling charge of the surface layer caused by film electrification can be suppressed. The surface resistivity value is preferably 1.0×10 9 Ω / □ or less, more preferably 1.0×10 8 Ω / □ or less. There is no particular lower limit, but the lower limit of 1.0×10 2 Ω / □ is a substantial lower limit. To control the surface resistivity value to the above range, for example, a method of controlling the amount of antistatic agent or release agent added to a preferred range described below or a method of using a carbon-based antistatic agent can be used.
[0055] As a third requirement of the resin layer X included in the laminated film of the present invention, the surface free energy needs to be greater than 20.0 mN / m and less than 30.0 mN / m. By setting the surface free energy to the above range, the surface layer such as ceramic slurry can be coated without coating depression in the process of coating the resin layer X of the laminated film, and the surface layer can be peeled off easily in the process of peeling off.
[0056] The surface free energy of the resin layer X in the present invention is preferably 22.0 mN / m or more and less than 28.0 mN / m, and more preferably 24.0 mN / m or more and less than 26.0 mN / m.
[0057] When the surface free energy of the resin layer X is less than 20.0 mN / m, coating depressions may occur in the process of coating the surface layer, resulting in a decrease in yield, and a large amount of release agent may be required, so that the release agent and antistatic agent are transferred from the resin layer X, which may have an adverse effect on the performance of the electronic component. On the other hand, when the surface free energy of the resin layer X is 30.0 mN / m or more, the surface layer may be severely peeled off in the process of peeling off the surface layer, resulting in film breakage of the surface layer.
[0058] In order to control the surface free energy of the resin layer X to be within the above-mentioned preferred range, for example, a method can be used in which, with respect to the XANES spectrum described later, the angle between the incident X-ray and the surface of the resin layer X is set to θ, the spectral intensity of 293.5 eV is set to I(θ) and is controlled to be I(15°)-I(90°)≥0.10, or a method in which the release agent uses the preferred material described later.
[0059] On the other hand, the second embodiment of the laminated film of the present invention is a laminated film having a resin layer X containing an antistatic agent on at least one surface of a thermoplastic resin substrate film, wherein the resin layer X needs to contain a long-chain alkyl resin, a melamine compound and an acrylic resin.
[0060] By adopting such a structure, the above-mentioned nitrogen atom to carbon atom ratio (N / C) calculated by high-resolution Rutherford backscattering method (HR-RBS method) and the average content ratio of nitrogen atoms to carbon atoms per 1nm thickness of the resin layer X calculated by the thickness (nm) of the resin layer X, the surface resistivity value, and the surface free energy can be fully satisfied, so that the light peelability of the resin layer, the antistatic property, the processability in the process of peeling the surface layer, the suppression of pollution caused by silicone, and the shedding of the antistatic agent, which are the effects of the present invention, can be achieved. It should be noted that the preferred materials used in the laminated film of the present invention are described later.
[0061] <Base film, polyester film>
[0062] The laminated film of the present invention has a resin layer X on at least one surface of the substrate film. The substrate film in the laminated film of the present invention is described in detail below. There is no particular restriction on the type of substrate film, but a polyester film is suitable from the viewpoint of heat resistance and cost (hereinafter, a polyester film used as a substrate film is sometimes referred to as a "substrate film" or "substrate".). The so-called polyester film refers to a film having polyester as a main component, and the so-called main component refers to a component contained in an amount exceeding 50 parts by mass when the entire resin constituting the film is set to 100 parts by mass.
[0063] In the present invention, the substrate film may contain particles. When particles are contained, the content thereof is preferably 3.0 parts by mass or less relative to the entire substrate film. By setting the content of the particles within the above range, a laminated film having excellent transparency can be obtained.
[0064] The polyester used in the base film of the laminated film of the present invention is described below. First, the so-called polyester is a general term for polymers having an ester bond in the main chain, and preferably a material having at least one selected from ethylene terephthalate, propylene terephthalate, ethylene 2,6-naphthalate, butylene terephthalate, propylene 2,6-naphthalate, α,β-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylic acid ethylene glycol ester as a constituent component can be used.
[0065] The polyester film using the above polyester is preferably a biaxially oriented polyester film. The so-called biaxially oriented polyester film refers to a polyester film oriented in two orthogonal directions, which shows a biaxially oriented pattern in wide-angle X-ray diffraction. The biaxially oriented polyester film is generally obtained by stretching an unstretched polyester sheet or film by about 2.5 to 5.0 times in the length direction and the width direction orthogonal to the length direction, and then performing a heat treatment to complete the crystal orientation. The thermal stability, especially dimensional stability, and mechanical strength of the biaxially oriented polyester film are sufficient, and the planarity is also good.
[0066] Furthermore, various additives such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, etc. may be added to the polyester film to such an extent that the properties thereof are not deteriorated.
[0067] The thickness of the polyester film is not particularly limited and can be appropriately selected according to the application and type, but is generally preferably 10 to 500 μm, more preferably 15 to 250 μm, and further preferably 20 to 200 μm in view of mechanical strength, handleability, etc. In addition, the polyester film can be any of a monolayer film, a composite film obtained by coextrusion, and a film obtained by laminating the obtained films by various methods.
[0068] The polyester film used in the substrate film of the laminated film of the present invention contains at least one of a biomass raw material and a recycled raw material, which is preferred from the viewpoint of reducing the environmental load. The so-called biomass here refers to an organic compound derived from a plant that has photosynthesized carbon dioxide and water. When the biomass is burned, it is usually converted into carbon dioxide and water again, so the biomass can be used as a so-called carbon-neutral renewable energy. In addition, the so-called biomass raw material refers to a polyester containing a structural unit derived from biomass.
[0069] When the ratio of the number of carbon atoms derived from plants to the total number of carbon atoms is defined as the biomass degree, for example, in the ethylene terephthalate unit, the biomass degree is theoretically 20% when only the ethylene glycol component is derived from plants. In order to make the biomass degree greater than 20%, terephthalic acid must also be derived from plants, which increases the effect of reducing the environmental load but increases the production cost. Regarding the ethylene glycol component and the terephthalic acid component, a component derived from petroleum and a component derived from plants can be used together.
[0070] From the viewpoint of reducing the effect of environmental load, the lower limit of the biomass degree of the polyester constituting the film is preferably 5%, more preferably 10%, and further preferably 13%. By having a biomass degree of 5% or more, the effect of reducing the environmental load can be expected. On the other hand, the upper limit of the biomass degree is more preferred when only considering the reduction of the environmental load, and 100% becomes the upper limit. However, from the viewpoint of both production cost and reducing the environmental load, it is preferably less than 20% in reality.
[0071] It should be noted that as a known method for analyzing the presence or absence of biomass raw materials, for example, the method using carbon isotopes ( 14 C) method.
[0072] The so-called recycled raw materials are raw materials that are recovered and reused from polyesters that have become chemical products once or multiple times. As recycled raw materials in the laminated film of the present invention, for example, the uncoated parts at both ends in the width direction that are cut off and removed in the manufacturing process of the laminated film of the present invention, the recycled products of other polyester films, and polyester products that are circulated in a form different from the film, such as PET bottles, etc. When the laminated film of the present invention is made into a film, the proportion of recycled raw materials in 100 parts by mass of polyester raw materials (recycling rate) is preferably 90 parts by mass or less. By suppressing the use of recycled raw materials to less than 90 parts by mass, the amount of highly crystalline polyester that becomes a chemical product once is suppressed, thereby reducing the thermal properties, transparency reduction, and coloring of the resulting laminated film.
[0073] <Resin layer X>
[0074] From the viewpoint of achieving both excellent releasability and antistatic properties, the laminated film of the present invention has a resin layer X on at least one surface of a base film.
[0075] From the viewpoint of preventing contamination caused by silicone, it is preferred that the resin layer X in the laminated film of the present invention has a ratio (P / K) [-] of the peak intensity (P) of the fragment derived from polydimethylsiloxane to the peak intensity (K) of the fragment detected with the maximum intensity in time-of-flight secondary ion mass spectrometry (GCIB-TOF-SIMS) of less than 0.01.
[0076] When the peak intensity ratio (P / K)[-] of the time-of-flight secondary ion mass spectrometry (GCIB-TOF-SIMS) is within the above preferred range, since the resin layer X has a small amount of components derived from polydimethylsiloxane, when the laminated film of the present invention is used as a process film for manufacturing electronic components, the organosilicon compound derived from polydimethylsiloxane is not easy to move (transfer) to the product side, and does not cause problems such as defective components of electronic components. From the viewpoint of feasibility, it is further preferably less than 0.001 (determination lower limit).
[0077] The method for adjusting the P / K of the resin layer X of the laminated film of the present invention to fall within the above range is not particularly limited, and an example thereof includes a method of using a release agent that does not contain silicone.
[0078] The laminated film of the present invention preferably satisfies I(15°)-I(90°)≥0.10 in the X-ray absorption near edge structure (XANES) spectrum of the carbon K absorption edge in the X-ray absorption fine structure (XAFS) spectrum measured by the partial electron yield method for the resin layer X, when the angle between the incident X-ray and the surface of the resin layer X is set to θ and the spectrum intensity of 293.5 eV is set to I(θ). I(15°)-I(90°) is less than 0.10, which means that the spectrum intensity does not change with respect to the angle θ between the incident X-ray and the surface of the resin layer X, that is, the irradiation direction of the X-ray, indicating that the orientation of the long-chain alkyl group is not anisotropic. On the other hand, the resin layer X satisfies I(15°)-I(90°)≥0.10, which means that the orientation direction of the long-chain alkyl group of the resin layer X is biased, specifically, the orientation in the vertical direction is promoted, thereby making it difficult for surface layer components such as ceramic slurry to penetrate into the resin layer X, and the peeling property of the surface layer can be improved. From the above viewpoint, it is more preferred that I(15°)-I(90°)≥0.30, and further preferably I(15°)-I(90°)≥0.50. By making I(15°)-I(90°) the above preferred range, the peeling force of the surface layer can be improved. It should be noted that, as a method of achieving I(15°)-I(90°)≥0.10, a method of adjusting the type and amount of a release agent (A) in the resin layer X can be cited. On the other hand, there is no particular limitation on the upper limit of I(15°)-I(90°), and the upper limit that can be achieved by practical materials and processes is approximately 10.00 or less, preferably 1.00 or less. The details of the release agent (A) are described later.
[0079] <Resin layer Y>
[0080] The laminated film of the present invention may include a resin layer Y on the surface opposite to the resin layer X. The resin layer Y may contain an antistatic agent to further suppress peeling static electricity when peeling a surface layer such as a ceramic slurry from the resin layer X.
[0081] The surface resistivity of the resin layer Y is preferably 1.0×10 10 Ω / □ or less. If the surface resistivity is 1.0×10 10 Ω / □ or less, the adhesion of foreign matter caused by film electrification and the electrification when the surface layer is peeled off from the resin layer X can be suppressed. The surface resistivity value is preferably 1.0×10 8 Ω / □ or less, more preferably 1.0×10 7 Ω / □ or less. There is no particular lower limit, but the lower limit of 1.0×10 2 Ω / □ is a substantial lower limit. In order to control the surface resistivity value to the above range, for example, a method of controlling the amount of the antistatic agent added to a preferred range described later or a method of using a carbon-based antistatic agent can be used.
[0082] <Coating composition>
[0083] Hereinafter, preferred coating compositions for forming the resin layer of the laminated film of the present invention will be described.
[0084] <Release agent (A)>
[0085] As the release agent that can be used in the first mode of the resin layer X of the laminated film of the present invention, resins containing long-chain alkyl groups, olefin resins, fluorine compounds, wax compounds, etc. can be cited. Among them, the resin containing long-chain alkyl groups is preferred in terms of being able to show good demoulding properties. On the other hand, from the perspective of adjusting the ratio of nitrogen atoms to carbon atoms (N / C) calculated by the HR-RBS method of the resin layer X of the laminated film of the present invention, and the average content ratio of nitrogen atoms to carbon atoms per 1nm thickness of the above-mentioned resin layer X to a preferred range, it is preferred to contain a reactive functional group as a side chain in addition to the long-chain alkyl group. That is, a particularly preferred mode as a release agent of the present invention is a copolymer resin having a long-chain alkyl group and a reactive functional group. Regarding reactive functional groups, hydroxyl, carboxyl, amino, glycidyl, isocyanate, vinyl, acryloyl, methacryloyl, etc. can be cited, but from the perspective of compatibility with water as a preferred solvent described later, it is particularly preferred to have a hydroxyl group.
[0086] From the viewpoint of making the resin layer X function as a release layer, the laminated film of the present invention preferably contains a long-chain alkyl resin as a release agent in the resin layer X, and the long-chain alkyl resin is heated from 25°C to 200°C at 20°C / min by a differential scanning calorimeter (DSC), and then cooled from 200°C to -50°C at 20°C / min. The exothermic peak temperature (Tc) is more preferably 35°C to 80°C, and further preferably 40°C to 70°C. By setting the exothermic peak temperature Tc to 30°C to 90°C, the long-chain alkyl of the release agent is easily oriented vertically, the surface free energy of the resin layer X can be controlled to a preferred range, and good coating properties and light peeling properties of the surface layer are exhibited.
[0087] In the second embodiment of the resin layer X of the laminated film of the present invention, the resin layer X contains a long-chain alkyl resin as a release agent (A).
[0088] The compound containing a long-chain alkyl group can use a commercial product, specifically, the "Ashiorexin" (registered trademark) series as a long-chain alkyl compound manufactured by Asia Industries, the "Pieroil" (registered trademark) series as a long-chain alkyl compound manufactured by Lion Spetsialty Chemicals, and the Lezem series as an aqueous dispersion of a long-chain alkyl compound manufactured by Chukyo Oils and Fats, etc. can be used. The release agent preferably has an alkyl group with a carbon number of 12 or more, and more preferably has an alkyl group with a carbon number of 16 or more. By making the carbon number of the alkyl group 12 or more, the hydrophobicity is improved, and sufficient demolding performance can be exhibited as a release agent. The upper limit of the carbon number of the alkyl group is not particularly limited, but if it is 25 or less, it is easy to manufacture, so it is preferred.
[0089] It should be noted that the presence or absence of an alkyl group having more than 12 carbon atoms can also be evaluated by using the intensity of a substance corresponding to the alkyl group in a signal obtained by, for example, TOF-SIMS (TOF-SIMS: time-of-flight secondary ion mass spectrometry) from the laminated film. In this case, by using a cutting method using an ion sputtering method in combination so that the measurement can be performed continuously in the depth direction (thickness direction), the distribution state of the compound containing the alkyl group can also be evaluated.
[0090] The above-mentioned release agent (A) is more preferably a block copolymer comprising a unit having an alkyl group. The above-mentioned release agent is a block copolymer comprising a unit having an alkyl group, so that the alkyl group is easily oriented, and the surface free energy of the resin layer X can be controlled to a preferred range, and the good coating and light peeling properties of the surface layer are shown. As a method for manufacturing a block copolymer, as long as it is an active radical polymerization method other than atom transfer radical polymerization (ATRP method), there is no particular limitation, and reversible addition-fragmentation chain transfer polymerization (RAFT method), a polymerization method using an organic tellurium compound (TERP method), a polymerization method using an organic antimony compound (SBRP method), a polymerization method using an organic bismuth compound (BIRP method) and an iodine transfer polymerization method and other active radical polymerization methods of exchange chain mechanisms, and various polymerization methods such as nitroxide free radical method (NMP method). Among them, from the viewpoint of the controllability of polymerization and the simplicity of implementation, RAFT method and NMP method are preferred.
[0091] <Binder resin (B)>
[0092] In the first embodiment of the resin layer X in the laminated film of the present invention, as the binder resin (B) forming the resin layer X, as long as the average content ratio of nitrogen atoms to carbon atoms per 1 nm, which is a parameter corresponding to the crosslinking density of the above-mentioned resin layer X, is 0.0030 [nm -1 ] above, any material can be used. As such a resin, for example, at least one selected from acrylic resins, epoxy resins and urethane resins is suitable, but acrylic resins are more preferably used from the viewpoint of adjusting the crosslinking density of the above-mentioned resin layer X and the viewpoint of the ease of introducing reactive functional groups. As for the reactive functional groups, hydroxyl, carboxyl, amino, glycidyl, isocyanate, vinyl, acryloyl, methacryloyl and the like can be cited, but from the viewpoint of adjusting the crosslinking density of the resin layer X, a copolymerized acrylic resin having a hydroxyl group or a carboxyl group is preferred, and a copolymerized acrylic resin having both a hydroxyl group and a carboxyl group is particularly preferred.
[0093] In the second embodiment of the resin layer X of the laminated film of the present invention, the resin layer X contains an acrylic resin as a binder resin (B).
[0094] The acrylic resin that can be used as the binder resin (B) is not particularly limited. As the monomer components constituting the binder resin (B), for example, alkyl acrylates, alkyl methacrylates (as the alkyl group, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, 2-ethylhexyl, lauryl, stearyl, cyclohexyl, phenyl, benzyl, phenylethyl, etc.), 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, acrylamide, methacrylamide, N-methylacrylamide, N-hydroxyethyl acrylate, 2-hydroxypropyl methacrylate, and other hydroxyl group-containing monomers can be used. Monomers containing amide groups such as -methyl methacrylamide, N-methylol acrylamide, N-methylol methacrylamide, N,N-dimethylol acrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, and N-phenyl acrylamide, monomers containing amino groups such as N,N-diethylaminoethyl acrylate and N,N-diethylaminoethyl methacrylate, monomers containing epoxy groups such as glycidyl acrylate and glycidyl methacrylate, monomers containing carboxyl groups or salts thereof such as acrylic acid, methacrylic acid, and salts thereof (lithium salts, sodium salts, potassium salts, etc.), etc. These monomers may be polymerized alone or in combination with other monomers for copolymerization.
[0095] The glass transition point (Tg) of the acrylic resin used as the binder resin (B) of the laminated film of the present invention is not particularly limited, but is preferably 0 to 90°C, and more preferably 10 to 80°C. By using an acrylic resin having a Tg of 0°C or higher, mold release properties are maintained even under high temperature and high humidity. Conversely, by using an acrylic resin having a Tg of 90°C or lower, the occurrence of cracks during stretching can be reduced in the preferred manufacturing method described later. In addition, the weight average molecular weight of the acrylic resin is preferably 100,000 or more, and more preferably 300,000 or more, which is preferred in terms of both film-forming properties and mold release properties.
[0096] Preferred acrylic resins used in the laminated film of the present invention include copolymers containing hydroxyalkyl acrylate, acrylamide, N-methylol acrylamide, glycidyl methacrylate, and acrylic acid, and particularly preferably copolymers containing 2-hydroxyethyl acrylate and acrylic acid.
[0097] In addition, examples of epoxy resins that can be used as the binder resin (B) include sorbitol polyglycidyl ether crosslinking agents, polyglycerol polyglycidyl ether crosslinking agents, diglycerol polyglycidyl ether crosslinking agents, and polyethylene glycol diglycidyl ether crosslinking agents. As the epoxy resin, commercially available products can be used, for example, epoxy compounds "Denacol" (registered trademark) EX-611, EX-614, EX-614B, EX-512, EX-521, EX-421, EX-313, EX-810, EX-830, EX-850, etc. manufactured by Nagase Chemtech Co., Ltd.), diepoxy / polyepoxy compounds (SR-EG, SR-8EG, SR-GLG, etc.) manufactured by Sakamoto Pharmaceutical Industries, Ltd., and epoxy crosslinking agents "EPICLON" (registered trademark) EM-85-75W or CR-5L manufactured by Dainippon Ink Industries, Ltd. can be preferably used. Among them, water-soluble substances are preferably used.
[0098] The urethane resin used as the binder resin (B) in the laminated film of the present invention is preferably a resin obtained by reacting a polyhydroxy compound with a polyisocyanate compound by a known urethane resin polymerization method such as emulsion polymerization or suspension polymerization.
[0099] Examples of the polyhydroxy compound include polyethylene glycol, polypropylene glycol, polyethylene glycol / propylene glycol, polybutylene glycol, 1,6-hexanediol, 1,4-butanediol, 1,5-pentanediol, diethylene glycol, triethylene glycol, polycaprolactone, polyhexamethylene adipate, polyhexamethylene sebacate, polytetramethylene adipate, polytetramethylene sebacate, trimethylolpropane, trimethylolethane, pentaerythritol, polycarbonate diol, and glycerin.
[0100] As the polyisocyanate compound, for example, hexamethylene diisocyanate, diphenylmethane diisocyanate, toluene diisocyanate, isophorone diisocyanate, an adduct of toluene diisocyanate and trimethylene propane, an adduct of hexamethylene diisocyanate and trimethylolethane, etc. can be used.
[0101] <Crosslinking agent (C)>
[0102] In the first embodiment of the resin layer X in the laminated film of the present invention, it is particularly preferred that the resin layer X contains a crosslinking agent (C) from the viewpoint of sufficiently carrying out the crosslinking reaction of the resin layer X, adjusting the ratio of nitrogen atoms to carbon atoms (N / C) calculated by the HR-RBS method, and the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X. Examples of the crosslinking agent (C) include melamine compounds, carbodiimide compounds, isocyanate compounds, Among them, the melamine compound has a large amount of reactive functional groups per unit molecular weight, and forms dense crosslinks by high temperature heating. When the laminated film is used as a release film, it can be easily peeled off when peeling the surface layer such as ceramic slurry from the laminated film, which can inhibit the fall of the antistatic agent.
[0103] As the melamine compound that can be used as a crosslinking agent (C), for example, melamine, a methylolated melamine derivative obtained by condensing melamine with formaldehyde, a compound partially or completely etherified by reacting a lower alcohol with methylolated melamine, and a mixture thereof, etc. can be used. In addition, as a melamine compound, it can be any one of a monomer or a condensate formed by a polymer of more than 2 polymers, or a mixture thereof. As the lower alcohol used for etherification, methanol, ethanol, isopropanol, n-butanol and isobutanol, etc. can be used. It is a substance having an imino group, a methylol group, or an alkoxymethyl group such as a methoxymethyl group or a butoxymethyl group as a functional group in one molecule, such as an imino type methylated melamine resin, a methylol type melamine resin, a methylol type methylated melamine resin, and a completely alkyl type methylated melamine resin, etc. Among them, it is most preferred to use a methylolated melamine resin.
[0104] In the second embodiment of the resin layer X of the laminated film of the present invention, the resin layer X contains a melamine compound as a crosslinking agent (C).
[0105] However, when an electron-conductive antistatic agent represented by a thiophene material is selected as the antistatic agent contained in the resin layer X and / or the resin layer Y of the laminated film of the present invention, the non-shared electrons of the N element of the amino resin are sometimes supplied to the electron-conductive antistatic material, thereby annihilating the holes as a single positive charge, thereby increasing the surface resistivity value. Therefore, when a thiophene material is used as the antistatic agent, it is preferable to select a carbodiimide compound, an isocyanate compound, or a crosslinking agent (C). That is, one of the preferred embodiments of the present invention is to simultaneously contain as a crosslinking agent (C) a carbodiimide compound, an isocyanate compound, The present invention comprises at least one oxazoline compound and a polythiophene compound as an antistatic agent (D) described below.
[0106] The carbodiimide compound that can be used as the crosslinking agent (C) is a compound having one or more carbodiimide groups or cyanamino groups in a tautomeric relationship as functional groups in the molecule. Specific examples of such carbodiimide compounds include dicyclohexylmethanecarbodiimide, dicyclohexylcarbodiimide, tetramethylxylylenecarbodiimide, and urea-modified carbodiimide, and one or more of these can also be used as a mixture.
[0107] Furthermore, examples of the isocyanate compound that can be used as the crosslinking agent (C) include toluene diisocyanate, diphenylmethane-4,4'-diisocyanate, meta-xylylene diisocyanate, hexamethylene-1,6-diisocyanate, 1,6-diisocyanate hexane, an adduct of toluene diisocyanate and hexanetriol, an adduct of toluene diisocyanate and trimethylolpropane, polyol-modified diphenylmethane-4,4'-diisocyanate, carbodiimide-modified diphenylmethane-4,4'-diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, meta-phenylene diisocyanate, and the like.
[0108] Furthermore, since isocyanate groups are prone to react with water, from the perspective of the pot life of the coating agent, blocked isocyanate compounds in which the isocyanate groups are masked with a blocking agent, etc., can be preferably used. In this case, heat is applied in the drying process after the polyester film is coated with the resin composition for forming the resin layer, so that the blocking agent is dissociated and the isocyanate groups are exposed, and as a result, the crosslinking reaction proceeds.
[0109] In addition, the crosslinking agent (C) may be used Azoline compounds are compounds having The substance having an oxazoline group as a functional group is preferably composed of at least one A monomer containing an oxazoline group, and a monomer obtained by copolymerizing at least one other monomer A copolymer of oxazoline.
[0110] As containing As a monomer of oxazoline group, 2-vinyl-2- Oxazoline, 2-vinyl-4-methyl-2- Oxazoline, 2-vinyl-5-methyl-2- Oxazoline, 2-isopropenyl-2- Oxazoline, 2-isopropenyl-4-methyl-2- Oxazoline and 2-isopropenyl-5-ethyl-2- Oxazoline, etc., and a mixture of one or more of them can also be used. Among them, 2-isopropenyl-2- Oxazoline is also easily available industrially and is suitable.
[0111] exist Among the oxazoline compounds, At least one other monomer used in the monomer containing an oxazoline group is capable of reacting with the monomer containing an oxazoline group. The monomers for copolymerization of the monomer with an oxazoline group can be, for example, acrylic acid esters or methacrylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, maleic acid, unsaturated nitriles such as acrylonitrile and methacrylonitrile, unsaturated amides such as acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxymethyl methacrylamide, vinyl esters such as vinyl acetate and vinyl propionate, vinyl ethers such as methyl vinyl ether and ethyl vinyl ether, olefins such as ethylene and propylene, halogen-containing α, β-unsaturated monomers such as vinyl chloride, 1,1-dichloroethylene, and vinyl fluoride, α, β-unsaturated aromatic monomers such as styrene and α-methylstyrene, etc. These can also be used as a mixture of one or more thereof.
[0112] <Antistatic agent (D)>
[0113] The laminated film of the present invention needs to contain an antistatic agent (D) as a component of the resin layer X and / or the resin layer Y. The type of the antistatic agent (D) is not particularly limited, and conductive carbon materials such as carbon nanotubes (CNTs), polymer materials having conductive structures represented by polythiophene structures, and acidic polymers in a free acid state can be used alone or in combination. In the present invention, from the viewpoint of having both antistatic properties and peeling properties, it is more preferable to use conductive carbon materials, and CNTs are particularly preferred.
[0114] One of the particularly preferred aspects of the resin layer X and / or the resin layer Y of the laminated film of the present invention is a composition comprising a resin containing a long-chain alkyl group as the release agent (A), an acrylic resin as the binder resin (B), a melamine compound as the crosslinking agent (C), and further a CNT as an antistatic agent (D). A further preferred aspect is a composition comprising a resin containing a long-chain alkyl group as a block copolymer as the release agent (A), a copolymerized acrylic resin having both a hydroxyl group and a carboxyl group as the binder resin (B), a melamine compound as the crosslinking agent (C), and further a CNT as an antistatic agent (D). By using such a combination, it is possible to have both releasability and antistatic properties while adjusting the ratio of nitrogen atoms to carbon atoms (N / C) calculated by the HR-RBS method and the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X.
[0115] The so-called CNT in the present invention refers to a seamless (without seams) tube in which a graphene sheet of a honeycomb structure consisting only of carbon atoms is rolled into a cylindrical shape. In essence, a graphene sheet rolled into one layer is called a single-layer CNT, a rolled into two layers is called a two-layer CNT, and a rolled into more than three layers is called a multilayer CNT. The CNT used in the present invention is preferably any one of a straight or curved single-layer CNT, a straight or curved two-layer CNT, a straight or curved multilayer CNT, or a combination thereof.
[0116] It should be noted that the so-called honeycomb structure refers to a network structure mainly formed by six-membered rings, and the CNT structure may have a ring structure other than six-membered rings, such as a five-membered ring or a seven-membered ring, in the curved portion of the tube or the closed portion of the cross section.
[0117] Regarding the CNT used in the present invention, among the above CNTs, straight or curved single-layer CNTs and straight and / or curved two-layer CNTs are preferably used from the perspective of conductivity. Single-layer CNTs and two-layer CNTs are excellent in dispersibility in solvents, durability, and manufacturing costs. On the other hand, multilayer CNTs with more than three layers have excellent dispersibility and manufacturing costs, but sometimes fail to obtain sufficient conductivity.
[0118] In addition, the CNT used in the present invention preferably has a diameter of 1 nm or more. In addition, the diameter of the CNT is preferably 50 nm or less, more preferably 10 nm or less. If the upper limit of the diameter is the above preferred range, the CNT is not easy to become a multilayer structure of more than 3 layers, and the conductive path is not easy to diverge between the layers, which can make the conductivity high. In addition, a large amount of CNT is not required, and the CNT does not fall off from the resin layer X and / or the resin layer Y, so it will not be transferred to the surface layer side such as the ceramic slurry, and the performance of the component is not reduced, and sufficient antistatic properties can be achieved with a small amount. On the other hand, the CNT with a diameter lower limit of the above preferred range is easy to manufacture and easy to obtain.
[0119] The aspect ratio of the CNT used in the present invention is preferably 100 or more. In addition, the aspect ratio of the CNT is preferably 5,000 or less. By making the aspect ratio of the CNT within the above range, the antistatic property of the resin layer X and / or the resin layer Y can be improved. If the aspect ratio of the CNT is within the above range, in the formation of the resin layer X and / or the resin layer Y, when the online coating method described later is used, the CNT is appropriately untied in the stretching process, the conductive path between the CNTs is not interrupted, and a network with sufficient gaps can be formed between the CNTs. If such a network structure is formed, good antistatic properties can be exhibited.
[0120] It should be noted that the aspect ratio is a value obtained by dividing the length (nm) of the CNT by the diameter (nm) of the CNT (length (nm) of the CNT / diameter (nm) of the CNT).
[0121] CNT with such characteristics is obtained by known manufacturing methods such as chemical vapor deposition, catalyst vapor deposition, arc discharge, laser evaporation, etc. When making CNT, fullerene, graphite, and amorphous carbon are generated as by-products at the same time, and catalyst metals such as nickel, iron, cobalt, and yttrium also remain, so it is preferred to remove these impurities and refine. In order to remove impurities, it is effective to carry out ultrasonic dispersion treatment together with acid treatment such as nitric acid and sulfuric acid, and it is further preferred to separate using a filter in order to improve purity.
[0122] Single-layer CNT and two-layer CNT are generally finer than multi-layer CNT. If they are evenly dispersed, the number of conductive paths per unit volume can be ensured to be more, and the conductivity is high. On the other hand, a large number of semiconductor CNTs are sometimes formed as by-products according to the manufacturing method. In this case, it is necessary to selectively manufacture or sort the conductive CNTs. Multilayer CNTs generally show conductivity, but if the number of layers is too large, the number of conductive paths per unit weight is reduced. Therefore, even in the case of using multilayer CNTs, the CNT diameter is preferably less than 50nm, more preferably less than 20nm, and more preferably less than 10nm. In addition, in the case of using single-layer CNT and two-layer CNT, in terms of its structure, a diameter of less than 20nm, more preferably less than 10nm is preferred from the viewpoint of antistatic properties.
[0123] When a polythiophene compound is used as an antistatic agent (D), for example, a compound having a structure in which the 3rd and 4th positions of the thiophene ring are substituted can be used. Further, a compound in which an oxygen atom is combined with a carbon atom at the 3rd and 4th positions of the thiophene ring can be used. It is sometimes difficult to make the coating liquid water-based when a hydrogen atom or a carbon atom is directly combined with the carbon atom. The above-mentioned compound can be manufactured by the method disclosed in Japanese Patent Publication No. 2000-6324, European Patent No. 602713, and U.S. Patent No. 5391472, but it can also be a method other than these.
[0124] For example, after obtaining 3,4-ethylenedioxythiophene using an alkali metal salt of 3,4-dihydroxythiophene-2,5-dicarboxylate as a starting material, potassium persulfate, ferric sulfate, and the previously obtained 3,4-ethylenedioxythiophene are introduced into an aqueous solution of polystyrenesulfonic acid to react, thereby obtaining a composition in which an acidic polymer such as polystyrenesulfonic acid and a polythiophene such as poly(3,4-ethylenedioxythiophene) are complexed.
[0125] As an aqueous coating composition containing poly-3,4-ethylenedioxythiophene and polystyrenesulfonic acid, a composition sold as Baytron P by HC Starck (Germany) or the like can be used.
[0126] On the other hand, as acidic polymers in the free acid state, for example, polymer carboxylic acids, polymer sulfonic acids, polyvinyl sulfonic acids, etc. can be cited. As polymer carboxylic acids, for example, polyacrylic acid, polymethacrylic acid, and polymaleic acid can be exemplified. In addition, as polymer sulfonic acids, for example, polystyrene sulfonic acid, in particular, polystyrene sulfonic acid is the most preferred in terms of antistatic properties. It should be noted that the free acid can be in the form of a partially neutralized salt. In addition, it can also be used in the form of copolymerization with other copolymerizable monomers such as acrylates, methacrylates, styrene, etc. The molecular weight of polymer carboxylic acids and polymer sulfonic acids is not particularly limited. Considering the stability and antistatic properties of the coating agent, its weight average molecular weight is preferably 1,000 or more and 1,000,000 or less, and more preferably 5,000 or more and 150,000 or less. It can be partially contained in the range of not damaging the characteristics of the invention. Alkali salts such as lithium salts and sodium salts, ammonium salts, etc. In the case of a salt in which the polyanion is neutralized, it can also be considered to act as a dopant. This is because the equilibrium between polystyrene sulfonic acid, which acts as a very strong acid, and the ammonium salt is shifted to the acidic side as the equilibrium reaction proceeds after neutralization.
[0127] In addition, the preferred contents of the release agent (A), the binder resin (B), the crosslinking agent (C), and the antistatic agent (D) in the resin composition for forming the resin layer X of the laminated film of the present invention are as follows.
[0128] <Content ratio of each resin composition in resin layer X>
[0129] As the resin composition for forming the resin layer X in the present invention, there is a preferred content of the release agent (A). Specifically, when the total of the release agent (A), the binder resin (B), and the cross-linking agent (C) is set to 100 parts by mass, the release agent (A) is preferably more than 10 parts by mass and less than 50 parts by mass, more preferably more than 20 parts by mass and less than 40 parts by mass, and more preferably less than 35 parts by mass. In the case where the release agent (A) is more than 10 parts by mass, the good peelability of the surface layer is shown. On the other hand, in the case where the release agent (A) is less than 50 parts by mass, in the case of being used as a release film, the release agent (A) is reduced from the falling off of the laminated film, and the pollution caused by the release agent (A) can be suppressed. Further, in the case where the amount of the release agent (A) is less than 50 parts by mass, the reduction of the effect of the antistatic agent (D) caused by the excessive presence of the release agent (A) on the surface can also be suppressed.
[0130] In addition, the content of cross-linking agent (C) also has a preferred range, specifically when the total of release agent (A), binder resin (B), and cross-linking agent (C) is set to 100 parts by mass, cross-linking agent (C) is preferably more than 40 parts by mass, more preferably more than 50 parts by mass, and particularly preferably more than 60 parts by mass. The above content is satisfied by cross-linking agent (C), so that it is easy to control the average content ratio of nitrogen atoms to carbon atoms (N / C) calculated by HR-RBS method and nitrogen atoms to carbon atoms per 1nm thickness of the above-mentioned resin layer X to a preferred range, and the demoulding property of various adherends is improved. On the other hand, about the upper limit of content, although it depends on the mixing amount of release agent (A) and binder resin (B), it is 90 parts by mass, preferably 85 parts by mass, and more preferably 75 parts by mass.
[0131] On the other hand, the mixing ratio of the binder resin (B) can be adjusted so that the above-mentioned release agent (A) and the crosslinking agent (C) are in a preferred content. However, when the total of the release agent (A), the binder resin (B), and the crosslinking agent (C) is 100 parts by mass, if the binder resin (B) is less than 5 parts by mass, it is sometimes difficult to support the resin layer X, resulting in the falling off of the resin layer X and the deterioration of the quality.
[0132] When the total of the release agent (A), the binder resin (B), and the cross-linking agent (C) is set to 100 parts by mass, the content of the antistatic agent (D) in the resin layer X used in the present invention is preferably 0.05 parts by mass or more and 20.0 parts by mass or less. More preferably, it is 0.5 parts by mass or more and 15 parts by mass or less, and more preferably 1.0 parts by mass or more and 10.0 parts by mass or less. If it is the above-mentioned preferred range, the resin layer X has sufficient antistatic performance. On the other hand, the cohesive force caused by the intermolecular force between the antistatic agent (D) will not be too high, and the dispersibility of the antistatic agent (D) will not be reduced, so the uniformity of the resin layer X is maintained, and the surface layer is not easy to become heavy peeling, which can effectively prevent the performance deterioration caused by the falling off of the antistatic agent (D) when the electronic component is made.
[0133] <Content ratio of each resin composition in resin layer Y>
[0134] The laminated film of the present invention may include a resin layer Y on the surface opposite to the resin layer X. The resin layer Y preferably contains a binder resin (B), a crosslinking agent (C), an antistatic agent (D), and may contain a release agent (A).
[0135] When the total amount of the release agent (A), the binder resin (B), and the crosslinking agent (C) is 100 parts by mass, the content of the binder resin (B) in the resin layer Y is preferably 5 parts by mass or more and 100 parts by mass or less. Preferably, it is 10 parts by mass or more and 90 parts by mass or less, and more preferably 20 parts by mass or more and 80 parts by mass or less. If the content of the binder resin (B) in the resin layer Y is within the above-mentioned preferred range, it is possible to effectively prevent the antistatic performance from being obtained due to poor film formation.
[0136] Regarding the content of the crosslinking agent (C) in the resin layer Y, when the total of the release agent (A), the binder resin (B), and the crosslinking agent (C) is set to 100 parts by mass, the crosslinking agent (C) is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, and particularly preferably 50 parts by mass or more. By satisfying the above content of the crosslinking agent (C), the fall-off of the antistatic agent (D) can be suppressed.
[0137] When the total amount of the release agent (A), the binder resin (B), and the crosslinking agent (C) is 100 parts by mass, the content of the antistatic agent (D) in the resin layer Y is preferably 0.05 parts by mass or more and 900 parts by mass or less. More preferably, it is 0.5 parts by mass or more and 700 parts by mass or less, and further preferably 1.0 parts by mass or more and 500 parts by mass or less. By making the content of the antistatic agent (D) within the above range, antistatic properties can be imparted to the resin layer Y.
[0138] In addition, when the release agent (A) is included in the resin layer Y, the content of the release agent (A) is preferably 50 parts by mass or less, and more preferably 30 parts by mass or less, when the total of the release agent (A), the binder resin (B), and the crosslinking agent (C) is 100 parts by mass. By setting the release agent (A) to the above range, the resin layer Y can be given a releasable property without damaging the antistatic property of the resin layer Y.
[0139] The resin composition for forming the resin layer X and / or the resin layer Y of the laminated film of the present invention may further include a particle component in addition to a release agent (A) and an adhesive resin (B), a crosslinking agent (C), and an antistatic agent (D). In particular, when the resin layer X and / or the resin layer Y of the laminated film of the present invention include a release agent (A), if the film surface is smooth, the slip property becomes higher than that of the conventional film. In the laminated film of the present invention, when the slip property is so high that the winding property deteriorates, by including such a particle component in the resin composition for forming the resin layer X and / or the resin layer Y, a protrusion shape can be formed on the surface of the resin layer X and / or the resin layer Y, and the transport property becomes good.
[0140] As particle components suitable for use in the laminated film of the present invention, oxide particles of elements located on and to the left of the oblique line connecting boron (B), silicon (Si), arsenic (As), tellurium (Te) and astatine (At) can be cited. As such particle components, for example, SiO2, TiO2, ZrO2, ZnO, CeO2, SnO2, Sb2O5, indium-doped tin oxide (ITO), phosphorus-doped tin oxide (PTO), Y2O3, La2O3, Al2O3, etc. can be cited. It should be noted that these particle components can be used alone or in combination of two or more. From the viewpoint of dispersion stability and refractive index, SiO2, TiO2, and ZrO2 are particularly preferred.
[0141] The particle component used in the resin layer X and / or resin layer Y of the laminated film of the present invention preferably has a number average particle diameter of 3 nm or more and 500 nm or less. More preferably, it is 20 nm or more and 400 nm or less, and further preferably 40 nm or more and 300 nm or less. The so-called number average particle diameter here refers to the particle diameter obtained by a transmission electron microscope (TEM). Specifically, the outer diameter of 10 particles present in the screen is measured by making the magnification 500,000 times, and the outer diameter of 100 particles is measured by repeating it for a total of 10 fields of view to obtain the number average particle diameter. The so-called outer diameter here represents the maximum diameter of the particle (i.e., the long diameter of the particle, indicating the longest diameter in the particle.), and the maximum diameter of the particle is also represented in the case of particles with a cavity inside. If the number average particle diameter of the particle component is 3 nm or more, there is a tendency that the van der Waals force between the particles is suppressed and the aggregation of the particles is reduced. On the other hand, the number average particle diameter of the particle component is 500 nm or less, so that the particles can be reduced from the resin layer X and / or the resin layer Y.
[0142] The method for producing the particle component is not particularly limited, and a method of surface treating the particle component with an acrylic resin can be cited, and specifically, the following methods (i) to (iv) can be exemplified. It should be noted that the so-called surface treatment in the present invention refers to a treatment in which an acrylic resin is adsorbed / attached to all or part of the surface of the particle component. The target effect can be obtained by any of the following methods (i) to (iv).
[0143] (i) A method in which a mixture of a particle component and an acrylic resin mixed in advance is added to a solvent and then dispersed.
[0144] (ii) A method of adding a particle component and an acrylic resin to a solvent in this order and dispersing them.
[0145] (iii) A method of preliminarily dispersing the particle component and the acrylic resin in a solvent and mixing the resulting dispersion.
[0146] (iv) A method in which the particle component is dispersed in a solvent and then an acrylic resin is added to the resulting dispersion.
[0147] In addition, as a device for dispersing, a dissolver, a high-speed mixer, a homogenizing mixer, a mill, a ball mill, a roller mill, a sand mill, a paint shaker, an SC mill, a ring mill, a pin mill, etc. can be used. Suitable conditions when using the above-mentioned device are that the rotation speed of the rotating shaft is a peripheral speed of 5 to 15 m / s, and the rotation time is 5 to 10 hours. Further, from the perspective of improving dispersibility, it is more preferred to use dispersed beads such as glass beads when dispersing. The bead diameter of the dispersed beads is preferably 0.05 to 0.5 mm, more preferably 0.08 to 0.5 mm, and further preferably 0.08 to 0.2 mm. It should be noted that mixing and stirring can be carried out by vibrating the container by hand, or using an electromagnetic stirrer, a stirring blade, or by ultrasonic irradiation, vibration dispersion, etc.
[0148] The content of the particle component in the resin layer X and / or the resin layer Y is preferably 0.5 mass parts or more and 10 mass parts or less relative to the total of 100 mass parts of the release agent (A), the binder resin (B), and the cross-linking agent (C). More preferably, it is 1 mass part or more and 7 mass parts or less, and further preferably 2 mass parts or more and 5 mass parts or less. By making the content of the particle component 0.5 mass parts or more and 10 mass parts or less relative to the total of the release agent (A), the binder resin (B), and the cross-linking agent (C), it is possible to impart a suitable surface shape without damaging the film-forming property of the resin layer X and / or the resin layer Y. As a result, the desired transportability can be fully expressed.
[0149] Furthermore, the resin layer X and / or the resin layer Y of the laminated film of the present invention may contain a crosslinking catalyst. By containing a crosslinking catalyst, the crosslinking reaction of the above-mentioned binder resin (B) and the crosslinking agent (C) during heat treatment is efficiently carried out, and the average content ratio of nitrogen atoms to carbon atoms per 1nm calculated by the ratio of nitrogen elements to carbon elements (N / C) measured by the HR-RBS method and the thickness (nm) of the resin layer X and / or the resin layer Y increases, that is, the crosslinking degree of the resin layer X and / or the resin layer Y becomes higher. As a result, when the resin layer X and / or the resin layer Y is coated with a surface layer, the penetration of the surface layer into the resin layer X and / or the resin layer Y is less likely to occur, and the peelability of the surface layer is easily improved. As a crosslinking catalyst, for example, an acidic catalyst such as p-toluenesulfonic acid and dodecylbenzenesulfonic acid, an amine salt-based catalyst, etc. can be used.
[0150] When preparing a resin composition, a solvent or a dispersion medium (hereinafter referred to as a "solvent") may be included. That is, various components may be dissolved or dispersed in a solvent to prepare a resin composition, which may be applied to a polyester substrate. When such a method is adopted, a film having a laminated resin layer may be obtained by drying the solvent after application and heating.
[0151] For the laminated film of the present invention, it is preferred to use an aqueous solvent as a solvent. Here, the so-called aqueous solvent refers to a substance in which water or water and an organic solvent soluble in water such as alcohols such as methanol, ethanol, isopropanol, butanol, ketones such as acetone, methyl ethyl ketone, ethylene glycol, diethylene glycol, propylene glycol, etc. are mixed in an arbitrary ratio. The reason is that by using an aqueous solvent, the rapid evaporation of the solvent in the heating process can be suppressed, and not only a uniform resin layer X and / or resin layer Y can be formed, but also excellent in terms of environmental load.
[0152] The resin composition for forming the resin layer in the laminated film of the present invention can be prepared by mixing and stirring the release agent (A), adhesive resin (B), cross-linking agent (C), antistatic agent (D) and aqueous solvent dispersed or dissolved in water as required in any order in a desired weight ratio. Then, various additives such as lubricants, inorganic particles, organic particles, surfactants, antioxidants, thermal initiators, etc. can also be mixed and stirred in any order as required to prevent the properties of the resin layer X and / or resin layer Y provided by the resin composition from deteriorating. The mixing and stirring methods can use a method of vibrating the container by hand, a method of stirring with an electromagnetic stirrer or a stirring blade, a method of using ultrasonic irradiation, vibration dispersion, etc.
[0153] <Manufacturing method>
[0154] In the laminated film of the present invention, the method of setting the resin layer X and / or the resin layer Y on at least one side of the substrate film can use any one of the online coating method and the offline coating method, preferably the online coating method. The so-called online coating method is a method of coating in the manufacturing process of the polyester film. Specifically, it refers to a method of coating at any stage from melt extrusion of the polyester resin to heat treatment and winding after biaxial stretching, usually, coated on an unstretched (unoriented) polyester film (A film) obtained after melt extrusion / quenching in a substantially amorphous state, a uniaxially stretched (uniaxially oriented) polyester film (B film) stretched in the length direction, or a biaxially stretched (biaxially oriented) polyester film (C film) stretched in the width direction before heat treatment.
[0155] On the other hand, the so-called off-line coating method is a method in which the film (C film) after the crystal orientation of the polyester film is completed by stretching the A film uniaxially or biaxially and heat-treating the film is coated with a resin composition in a process different from the film forming process.
[0156] In the present invention, it is preferred to manufacture the laminated film by an online coating method. By manufacturing by the online coating method, for example, compared with forming the resin layer X and / or the resin layer Y by offline coating on a biaxially stretched PET film, the laminated film can be manufactured at a lower cost, and the dense crosslinking of the resin layer X and / or the resin layer Y can be promoted by performing a high-temperature heat treatment of 200°C or more, which is substantially impossible by offline coating, and when a coating agent such as a ceramic slurry is applied, the adhesive component contained in the slurry is suppressed from penetrating into the resin layer X and / or the resin layer Y, so that the surface layer can be peeled off lightly, and further, the antistatic agent is retained in the resin layer X and / or the resin layer Y by dense crosslinking, so that the antistatic agent can be suppressed from falling off. In particular, a manufacturing method in which a coating composition is applied to at least one side of a polyester film before crystal orientation is completed, the film is stretched in at least a uniaxial direction, and then heat-treated to complete crystal orientation of the polyester film is preferred from the viewpoints of manufacturing cost and dimensional stability after heat treatment, heat shrinkage characteristics, and density of the resin layer X and / or resin layer Y.
[0157] <Coating method>
[0158] The resin composition can be applied to the polyester film by any known coating method, such as bar coating, reverse coating, gravure coating, die coating, blade coating, etc. Here, the adhesion between the polyester film and the resin layer X and / or the resin layer Y will be described.
[0159] If the resin layer X and / or the resin layer Y are provided on the polyester film by a conventional off-line coating method, when the resin layer X and / or the resin layer Y contain a release agent, the resin layer X and / or the resin layer Y having a low surface energy lacks adhesion to the film, and thus, when the film roll is rewound, the resin layer is sometimes cut, and the peeling force is deteriorated. However, when the resin layer X and / or the resin layer Y are laminated by an online coating method, by applying the coating composition to the polyester film before the crystal orientation is completed, a very small amount of the coating composition penetrates into the polyester film, and thus the resin layer X and / or the resin layer Y can be given adhesion to the thermoplastic resin substrate. As a result, excellent peeling force can be achieved.
[0160] <Method for Forming Resin Layer X and / or Resin Layer Y>
[0161] In the present invention, it is preferred that the resin layer X and / or the resin layer Y be formed by applying the coating composition on at least one side of the polyester film and then drying it. In the present invention, when the coating composition contains a solvent, it is preferred to use an aqueous solvent as the solvent. By using an aqueous solvent, the rapid evaporation of the solvent in the drying process can be suppressed, and not only a uniform and high-quality resin layer X and / or resin layer Y can be formed, but also the environmental load is excellent.
[0162] Here, the aqueous solvent refers to water, or a mixture of water and a water-soluble organic solvent such as alcohols such as methanol, ethanol, isopropanol, and butanol, ketones such as acetone and methyl ethyl ketone, and glycols such as ethylene glycol, diethylene glycol, and propylene glycol in an arbitrary ratio without phase separation.
[0163] The coating method of the coating composition to the film is as described above, and is preferably an in-line coating method. Specifically, it refers to a method of coating at any stage from melt extrusion of the polyester resin to heat treatment after biaxial stretching and winding up, and is usually coated on any of the films of the unstretched (unoriented) film (A film) obtained after melt extrusion / quenching and being substantially amorphous, the uniaxially stretched (uniaxially oriented) film (B film) stretched in the length direction or width direction, or the biaxially stretched (biaxially oriented) film (C film) stretched in the width direction or length direction before heat treatment.
[0164] In the present invention, it is preferred to apply the coating composition to any of the A film and the B film before the completion of crystal orientation, then stretch the film in a uniaxial direction or a biaxial direction, and heat-treat the film at a temperature higher than the boiling point of the solvent to complete the crystal orientation of the film and simultaneously provide the resin layer X and / or the resin layer Y. According to this method, the film formation and the coating and drying of the coating composition (i.e., the formation of the resin layer X and / or the resin layer Y) can be performed simultaneously, so in addition to the advantage in terms of manufacturing cost, it is also easy to ensure the above-mentioned substrate adhesion.
[0165] Among them, the method of applying the coating composition to a film (B film) uniaxially stretched in the length direction, then stretching it in the width direction and performing heat treatment is excellent. The reason is that compared with the method of applying the coating composition to an unstretched film and then performing biaxial stretching, the stretching process is one less, so defects and cracks of the resin layer X and / or the resin layer Y caused by stretching are not easy to occur, and a resin layer X and / or a resin layer Y with excellent smoothness can be formed. In addition, as described above, by applying the coating composition to the film before the completion of the crystal orientation, the adhesion between the resin layer X and / or the resin layer Y and the polyester film can be given.
[0166] Therefore, the preferred method for forming the resin layer X and / or the resin layer Y in the present invention is to apply a coating composition using an aqueous solvent on a polyester film using an online coating method, and then dry and heat treat the coating composition. In addition, a method of applying the coating composition online on the B film after uniaxial stretching is more preferred. In the method for manufacturing a laminated film of the present invention, in order to complete the removal of the solvent of the coating composition, drying can be carried out in a temperature range of 80 to 130°C. In addition, in order to complete the crystal orientation of the polyester film and the thermal curing of the coating composition and complete the formation of the resin layer X and / or the resin layer Y, the heat treatment can be carried out in a temperature range of 160 to 240°C. 180 to 240°C is particularly preferred. When the heat treatment temperature is less than 160°C, sometimes not only the performance of the polyester as the substrate film is reduced, such as the heat resistance of the substrate is reduced, but also it is difficult to obtain the dense crosslinking of the resin layer X and / or the resin layer Y, resulting in deterioration of the peeling property of the surface layer and the shedding of the antistatic agent.
[0167] Furthermore, the solid content concentration of the coating composition is preferably 40 parts by mass or less. By setting the solid content concentration to 40 parts by mass or less, good coating properties can be imparted to the coating composition, and a laminated film having a uniform resin layer X and / or resin layer Y can be produced.
[0168] It should be noted that the so-called solid content concentration represents the ratio of the mass of the coating composition to the mass of the coating composition minus the mass of the solvent (i.e., [solid content concentration] = [(mass of the coating composition) - (mass of the solvent)] / [mass of the coating composition].).
[0169] <Method for producing laminated film>
[0170] Next, the method for producing the laminated film of the present invention will be specifically described using an example in which the substrate film is a polyethylene terephthalate (PET) film, but the laminated film of the present invention is not limited to that obtained by this production method.
[0171] First, after the PET particles are fully vacuum dried, they are supplied to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to produce an unstretched (unoriented) PET film (A film). The A film is stretched 2.5 to 5.0 times in the length direction with a roller heated to 80 to 120°C to obtain a uniaxially oriented PET film (B film). A coating composition modulated to a specified concentration is applied to one side of the B film. At this time, the coated surface of the PET film can also be subjected to a surface treatment such as a corona discharge treatment before coating. By performing a surface treatment such as a corona discharge treatment, the wettability of the resin composition to the PET film can be improved, the depression of the resin composition can be prevented, and a uniform coating thickness can be achieved.
[0172] After coating, the end of the PET film is gripped with a clamp and directed to a heat treatment area (preheating area) of 80 to 130°C to dry the solvent of the coating composition, and after drying, it is stretched 1.1 to 5.0 times in the width direction. Then it is directed to a heating area (heat treatment area) of 150 to 250°C for 1 to 30 seconds of heat treatment to complete the crystal orientation and the formation of the resin layer X and / or the resin layer Y. It can be considered that the crosslinking of the resin layer X and / or the resin layer Y is promoted by this heating process (heat treatment process). It should be noted that in this heating process (heat treatment process), a relaxation treatment of 3 to 15% can also be implemented in the width direction or the length direction as needed. By operating in this way, a laminated film can be obtained, and the obtained laminated film can also be wound into a roll to make a film roll.
[0173] Example
[0174] Hereinafter, the laminated film of the present invention will be described in more detail using Examples, but the laminated film of the present invention is not limited thereto.
[0175] <Methods for measuring properties and evaluating effects>
[0176] The method for measuring the characteristics and the method for evaluating the effects in the present invention are as follows.
[0177] (1) Thickness dx and dy of resin layer X and resin layer Y
[0178] The laminated film was stained with RuO4 and / or OsO4. Next, the laminated film was frozen and cut parallel to the film thickness direction to obtain 10 ultrathin section samples (10 pieces) for cross-sectional observation of the resin layer. Each sample cross section was observed at 10,000 to 1,000,000 times using a TEM (transmission electron microscope: H7100FA type manufactured by Hitachi, Ltd.) to obtain a cross-sectional photograph. The thickness of the resin layer was measured from the cross-sectional photographs of the 10 points (10 pieces) of the sample using the length measurement function of the microscope, and the obtained measured values were averaged to form the thickness dx of the resin layer X of the laminated film and the thickness dy of the resin layer Y.
[0179] (2) The ratio of nitrogen atoms to carbon atoms (N / C) calculated by high-resolution Rutherford backscattering method (HR-RBS method) and the average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X
[0180] The Rutherford backscattering method is an analysis method that irradiates an ion beam to a sample to be measured and analyzes the energy of ions that are backscattered (Rutherford scattered) by collision with elements in the sample, thereby obtaining information about the elements in the sample. As information obtained by analyzing the energy of ions scattered by the Rutherford backscattering method, in addition to information on the type of elements that collided in the sample and information on the number of elements, relative information related to the location (i.e., depth) of the element that exists based on the energy change until the element collides with the element can also be cited.
[0181] The measurement device used was a Pelletron 3SDH manufactured by National Electrostatics Corporation. The energy was set to 2,300 keV and the beam diameter was set to of 4 He ++ The ions are irradiated to the sample at an incident angle of 75° relative to the sample surface, and the scattered 4 He ++ Ions were detected at scattering angles of 160° and 146° by a polarized magnetic field energy analyzer. The sample current was 7nA, the irradiation was 40μC, and the measurement energy range was 200-1,000keV. The obtained spectrum was simulated and fitted, and converted into a depth profile, and the surface density [atoms / cm 2 ]. It should be noted that in order to reduce damage such as burns caused by the measurement, the measurement was carried out at 10 points with staggered positions, and the accumulated data was used in the analysis. First, the obtained data was analyzed, and the data derived from the substrate and the data derived from the resin layer X were divided. Specifically, the nitrogen element (N) not contained in the substrate of the laminated polyester film of the embodiment of the present invention was used as an indicator, and the threshold value at which the nitrogen element becomes undetectable was used as the boundary between the substrate and the resin layer X, and the analysis was carried out based on the relative position information. Next, the surface density of the nitrogen element obtained from the resin layer [atoms / cm 2 ] divided by the surface density of carbon element [atoms / cm 2 ], the ratio of nitrogen atoms to carbon atoms (N / C) was calculated. The average content ratio of nitrogen atoms to carbon atoms per 1 nm thickness of the resin layer X was obtained by dividing by the thickness of the resin layer X measured by (1).
[0182] (3) Surface resistivity
[0183] The surface resistivity value was measured after the laminate film to be measured was prepared and placed at a relative humidity of 23% and 25°C for 24 hours. In this atmosphere, a digital ultra-high resistance / micro current meter R8340A and a Registibi Chienba 12702A (made by Adban Test Co., Ltd., main electrode: Φ50 mm, counter electrode: Φ103 mm) were used. After applying a voltage of 100 V for 10 seconds, the measurement was performed. The unit of the surface resistivity is Ω / □. The surface of the resin layer X and the resin layer Y of the laminate film on the opposite side to the substrate film was evaluated, and the average value of the total 10 measurements was set as the surface resistivity value of the sample.
[0184] (4) Surface free energy
[0185] First, the laminated film was placed in an atmosphere at room temperature 23°C and relative humidity 65% for 24 hours. Then, in the same atmosphere, the contact angle of each of the four solutions of pure water, ethylene glycol, formamide, and diiodomethane was measured at 5 points on the surface side of the resin layer X of the laminated film using a contact angle meter CA-D (manufactured by Kyowa Interface Science Co., Ltd.). The average of the three-point measurement values excluding the maximum and minimum values of the five-point measurement values was set as the contact angle of each solution.
[0186] Next, using the contact angles of the four solutions obtained, the surface free energy (γ) of a solid can be separated into dispersion force components (γ S d ), polar force component (γ S p ), and hydrogen bonding components (γ S h ) these three components, the geometric mean method of the formula (extended Fowkes formula) "is used to calculate the dispersion force, polar force, hydrogen bond force and surface energy which is the sum of the dispersion force and polar force of the present invention.
[0187] The specific calculation method is shown below. The meaning of each symbol is described below. S L When is the tension at the interface between a solid and a liquid, mathematical formula (i) holds true.
[0188] γ S L : Surface energy of resin layer X and known solutions listed in Table
[0189] γ S : Surface energy of resin layer X
[0190] γ L : The surface energy of known solutions listed in the table
[0191] γ Sd : Dispersion component of the surface energy of the resin layer X
[0192] γ S p : Polar force component of the surface energy of the resin layer X
[0193] γ S h : Hydrogen bonding component of the surface energy of the resin layer X
[0194] γ L d : The dispersion component of the surface energy of the known solutions listed in the table
[0195] γ L p : The polar force components of the surface energy of known solutions listed in the table
[0196] γ L h : The hydrogen bonding component of the surface energy of the known solutions listed in the table
[0197] γ S L =γ S +γ L -2(γ S d γ L d ) 1 / 2 -2(γ S p γ L p ) 1 / 2 -2(γ S h γ L h ) 1 / 2 ···Mathematical formula (i).
[0198] In addition, the state when a smooth solid surface and a liquid droplet are in contact with each other at a contact angle (θ) is expressed by the following formula (Young's formula).
[0199] γ S =γ S L +γ L cosθ···Mathematical formula (ii).
[0200] When these mathematical expressions (i) and (ii) are combined, the following expression is obtained.
[0201] (γ S d γ L d )1 / 2 +(γ S p γ L p ) 1 / 2 +(γ S h γ L h ) 1 / 2 =γ L (1+cosθ) / 2···Mathematical formula (iii).
[0202] In fact, the contact angle (θ) and the surface tension components (γ) of the known solutions were compared in four solutions of water, ethylene glycol, formamide, and diiodomethane. L d , γ L p , γ L h ) is substituted into formula (iii) to solve the four simultaneous equations. As a result, the surface energy (γ) and dispersion force component (γ S d ), polar force component (γ S p ), and hydrogen bonding components (γ S h ).
[0203] (5) Analysis method of composition of the surface of resin layer X
[0204] The composition of the surface of the resin layer X of the laminated film was analyzed using GCIB-TOF-SIMS (GCIB: gas cluster ion beam, TOF-SIMS: time-of-flight secondary ion mass spectrometry). The measurement conditions are as follows. In the graph obtained by the measurement, the peak intensity of the fragment detected with the maximum intensity is set as K, and the fragment derived from polydimethylsiloxane (SiCH3 + The peak intensity of the fragment ion (M / Z=43)) was defined as P, and the ratio P / K was calculated. When P / K<0.1, it was determined that the resin layer X did not substantially contain the organosilicon compound.
[0205] <Sputtering conditions>
[0206] Ion source: Argon cluster ion beam
[0207] <Testing conditions>
[0208] Primary ion: Bi 3++ (25keV)
[0209] Secondary ion polarity: Negative
[0210] Mass range: m / z 0~1,000
[0211] Measuring range: 200×200μm 2 .
[0212] (6) Exothermic peak temperature (Tc) during cooling by differential scanning calorimeter (DSC)
[0213] 1 g of the release agent (A) or the resin layer X cut from the surface of the laminated film is added to an aluminum cup with a diameter of 5 cm, and dried in a hot air furnace at a temperature of 80°C for 24 hours to produce a solid sample of the dried release agent (A) or the resin layer X. 3 mg of the produced solid sample was taken and measured using a differential scanning calorimeter (DSC6220 manufactured by Hitachi HiTech Science). First, in a nitrogen atmosphere, the temperature was raised from 25°C to 200°C at 20°C / min, and maintained at 200°C for 5 minutes. Then, the temperature was lowered to -50°C at 20°C / min, and the peak temperature of the curve obtained during the temperature drop was measured. The average value of the three measurements was set as (Tc). At this time, although sometimes two or more melting peak temperatures are observed in the above-mentioned temperature range, and sometimes it becomes a peak temperature observable in a multi-stage DSC graph called a shoulder (observed in the case of a graph in which two or more peaks overlap), in the present invention, the peak temperature with the largest absolute value of the heat (unit: mW) on the vertical axis of the DSC graph is set to (Tc).
[0214] (7) X-ray absorption near-edge structure (XANES) spectrum
[0215] The side opposite to the resin layer X surface of the laminated film was polished to adjust the thickness of the laminated film to 10 μm. A piece of the laminated film after polishing was cut into 12 mm in length and 6 mm in width, and used as a measurement sample. Next, the resin layer X surface of the measurement sample was irradiated with X-rays, and the absorption was measured to measure the X-ray absorption fine structure (XAFS: X-ray Absorption Fine Structure) spectrum. The measurement conditions and analysis conditions are as follows.
[0216] Experimental facility: Ritsumeikan University SR Center
[0217] Experimental station: BL11
[0218] Beam splitter: Diffraction grating beam splitter
[0219] Absorption edge: K (284.2 eV) absorption edge of carbon
[0220] E0: 287.319eV
[0221] Pre-edge range: -20~10eV
[0222] Normalization range: 15~70eV
[0223] Detection method: Partial electron yield method using multichannel plate measurement
[0224] Horizontal axis correction: The π of highly oriented pyrolytic graphite * Peak corrected to 255.5 eV
[0225] In the above XAFS spectrum, regarding the X-ray absorption near edge structure (XANES) spectrum of the K absorption edge of carbon, the angle between the incident X-ray and the length direction vector of the resin layer X plane of the laminated film is set to θ, and the spectrum intensity of 293.5 eV obtained by the partial electron yield method is set to I(θ). The value obtained by subtracting the spectrum intensity I(90°) when θ is 90° from the spectrum intensity I(15°) when θ is 15° is set to I(15°)-I(90°).
[0226] (8) Peel strength of surface layer
[0227] The laminated film was cut into a size of 20 mm in width and 70 mm in length, and the ceramic slurry obtained by mixing the following composition was applied to the resin layer X of the laminated film of the present invention using an applicator with the longitudinal direction as the traveling direction in a manner to a final thickness of 2 μm, and then dried in a hot air oven at 100°C for 1 minute to form a ceramic sheet (surface layer). Using a peeling device "VPA-2" manufactured by Kyowa Interface Science Co., Ltd. and a 1N force sensor, the opposite side of the surface layer was fixed to a measuring table, and a 90° peeling test was performed with the longitudinal direction as the traveling direction at a peeling speed of 300 mm / minute.
[0228] The average value of the peel force in 15 to 35 mm was calculated from the peel force (N)-displacement (mm) graph obtained by the measurement. The measurement was performed 5 times, and the average of the three times excluding the maximum and minimum values was set as the peel force of the laminated film, and the following evaluation was performed. A and above were set as good, and B was set as a level with no practical problems.
[0229] S: less than 20mN / cm
[0230] A: 20mN / cm or more and less than 40mN / cm
[0231] B: 40mN / cm or more and less than 80mN / cm
[0232] C: 80mN / cm or more
[0233] <Production of ceramic slurry>
[0234] · BaTiO3 (manufactured by Sakai Chemical Industry Co., Ltd.) 85 parts by mass
[0235] · Polyvinyl butyral ("ESLECK (registered trademark)" BM-2 manufactured by Sekisui Chemical Co., Ltd.) 15 parts by mass
[0236] ·Dioctyl phthalate (manufactured by Kanto Chemical Co., Ltd.) 5 parts by mass
[0237] ·Toluene 150 parts by mass
[0238] · 150 parts by mass of ethanol (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0239] Zirconia balls with a diameter of 1 mm (YTZ-1 manufactured by Nikkato Corporation) were added in an amount 2.5 times the weight of the slurry solution, and the mixture was stirred at 55 rpm for 72 hours using a stirring rotor (MIX ROTOR VNRC-5 manufactured by AS ONE).
[0240] (9) Charging of the surface layer during peeling
[0241] The release film with a ceramic sheet obtained in (8) above, in which a ceramic sheet layer (surface layer) is laminated on the surface layer side of the laminate film, is cut into pieces with a width of 20 mm and a length of 80 mm. Next, the surface layer is peeled off from the resin layer surface of the release film by the peeling test of (8) (peeling speed 300 mm / min). Using a digital electrostatic potential meter (manufactured by Kasuga Electric Co., Ltd., KSD-0103), the voltage on the peeled ceramic sheet side is measured at 20°C in an atmosphere of 50% RH, and the absolute value of the voltage is evaluated using the following four criteria, with S being set to very good, A being set to good, and B being set to a level that is not a problem in practical use.
[0242] S: ≤0.05kV
[0243] A: More than 0.05kV and less than 0.20kV
[0244] B: more than 0.20kV and less than 0.50kV
[0245] C:>0.50kV
[0246] (10) Evaluation of antistatic agent shedding
[0247] The laminate film was cut into sizes of 110 mm and 110 mm, and the ceramic slurry prepared in (8) was applied to the resin layer X of the laminate film of the present invention using a coater in a manner such that the final thickness became 5 μm. The film was then dried in a hot air furnace at 100°C for 1 minute to form a ceramic sheet (surface layer). The surface resistivity (SR1) of the surface layer was measured using the method (3).
[0248] The spacer on one side of 3M's acrylic adhesive sheet ("OCA" (registered trademark) 8146-2) was peeled off and adhered to the surface layer of the ceramic laminate. The acrylic adhesive sheet was then peeled off from the laminate film, and the surface layer was transferred to the acrylic adhesive sheet side. The surface resistivity value (SR2) of the transferred surface layer was measured by the method (3), and the shedding property of the antistatic agent was evaluated by (SR1) / (SR2), with A being set to a good level and B being set to a level that is not a problem in practical use.
[0249] A: (SR1) / (SR2) less than 10 (no transfer)
[0250] B: (SR1) / (SR2) is 10 or more and less than 100
[0251] C: (SR1) / (SR2) is 100 or more
[0252] <Resins etc. used in the production of laminated films>
[0253] <Release agent (A)>
[0254] Release agent (A-1): long chain alkyl resin 1
[0255] 200 parts by mass of xylene and 600 parts by mass of octadecyl isocyanate were added to a 4-necked flask and heated under stirring. From the moment when xylene began to reflux, 100 parts by mass of polyvinyl alcohol with an average degree of polymerization of 500 and a saponification degree of 88 mol% was added in small portions at intervals of 10 minutes for about 2 hours. After the addition of polyvinyl alcohol was completed, the reaction was terminated by further refluxing for 2 hours. The reaction mixture was cooled to about 80°C and added to methanol, and the reaction product was precipitated as a white precipitate. After filtering and separating the precipitate, 140 parts of xylene were added and heated to completely dissolve it. Then, methanol was added again to precipitate it. After repeating this operation several times, the precipitate was washed with methanol and dried and crushed to obtain a resin (A-1) containing a long-chain alkyl group: a polymethylene group as the main chain and an alkyl group with 18 carbon atoms in the side chain. ). It was diluted with water and adjusted to 20 parts by mass.
[0256] Release agent (A-2): long chain alkyl resin 2
[0257] In a 25 mL pressure-resistant glass polymerization ampoule, methyl methacrylate (hereinafter, MMA) (manufactured by Kanto Chemical Co., Ltd.), α,α'-azobisisobutyronitrile (hereinafter, AIBN) (manufactured by Kanto Chemical Co., Ltd.) as a polymerization initiator, cumyl dithiobenzoate (hereinafter, CDB) as a RAFT agent, and toluene as a solvent were added at a weight (g) of MMA / CDB / AIBN / toluene = 2.92 / 0.03 / 0.007 / 2.27. Next, the mixed solution in the ampoule was degassed twice by freeze degassing, and the ampoule was sealed and heated in an oil bath at 100°C for 18 hours to obtain a polymerization solution 1. Next, in the reaction solution in the ampoule, behenyl acrylate, AIBN as a polymerization initiator, and toluene as a solvent were added at a weight (g) of behenyl acrylate / AIBN / toluene = 1.37 / 0.003 / 1.3, and after two freeze degassings, the ampoule was sealed and heated at 100°C for 48 hours. Then, the polymerization solution 1 was added dropwise to 20 times the mass of hexane, and stirred to precipitate solids. The obtained solid was filtered and vacuum dried at 40°C overnight to obtain a long-chain alkyl resin (A-2) having an alkyl group with 22 carbon atoms. The obtained long-chain alkyl resin (A-2) was emulsified as follows to prepare an aqueous resin emulsion. 375 g of water was added to a 1 L homomixer, followed by 45 g of polyoxyethylene nonylphenyl ether, 30 g of polyoxyethylene polyoxypropylene glycol, 200 g of long-chain alkyl resin (A-2), and 150 g of toluene, and then heated to 70° C. and stirred uniformly. The mixed solution was transferred to a pressurized homogenizer and emulsified, and then the toluene was distilled off under reduced pressure while heating.
[0258] Release agent (A-3): long chain alkyl resin 3
[0259] A resin containing a long-chain alkyl group (A-3: having a polymethylene group as a main chain and an alkyl group having 12 carbon atoms in a side chain) was obtained by synthesizing it in the same manner as the resin containing a long-chain alkyl group (A-1), except that dodecyl isocyanate was used instead of octadecyl isocyanate.
[0260] Release agent (A-4): long chain alkyl resin 4
[0261] An aqueous coating liquid (A-4) was prepared by dissolving an acrylic resin having a long-chain alkyl group having the following copolymerization composition in water containing 5 wt % of isopropyl alcohol and 5 wt % of n-butyl cellosolve. The long-chain alkyl group of lauryl methacrylate had 12 carbon atoms.
[0262] <Copolymer components>
[0263] Lauryl methacrylate 70 wt%
[0264] Methacrylic acid 25 wt%
[0265] 2-Hydroxyethyl methacrylate 5 wt%.
[0266] Release agent (A-5): Silicone release agent
[0267] 100 parts by mass of a thermosetting silicone resin [manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KS-847H"] and 1 part by mass of a catalyst [manufactured by Shin-Etsu Chemical Co., Ltd., trade name "CAT-PL-50T"] were diluted with toluene to obtain a solution having a solid content concentration of 1.5 parts by mass.
[0268] <Binder resin (B)>
[0269] Binder resin (B-1): acrylic resin (containing hydroxyl groups)
[0270] In a stainless steel reaction container, methyl methacrylate (α), ethyl acrylate (β), 2-hydroxyethyl acrylate (γ), and acrylonitrile (δ) were added in a mass ratio of (α) / (β) / (γ) / (δ)=60 / 32 / 6 / 2, and 2 parts by mass of sodium dodecylbenzenesulfonate as an emulsifier were added to a total of 100 parts by mass of (α) to (δ) and stirred to prepare a mixed solution 1. Next, a reaction device equipped with a stirrer, a reflux cooling tube, a thermometer, and a dropping funnel was prepared. 60 parts by mass of the above mixed solution 1, 200 parts by mass of isopropyl alcohol, and 5 parts by mass of potassium persulfate as a polymerization initiator were added to the reaction device, and heated to 60°C to prepare a mixed solution 2. The mixed solution 2 was kept in a heated state at 60°C for 20 minutes. Next, a mixed solution 3 consisting of 40 parts by mass of the mixed solution 1, 50 parts by mass of isopropyl alcohol, and 5 parts by mass of potassium persulfate was prepared. Next, the mixed solution 3 was added dropwise to the mixed solution 2 over 2 hours using a dropping funnel to prepare a mixed solution 4. Then, the mixed solution 4 was kept heated to 60°C for 2 hours. The obtained mixed solution 4 was cooled to 50°C or less and then transferred to a container equipped with a stirrer and a decompression device. 60 parts by weight of 25% ammonia water and 900 parts by weight of pure water were added thereto, and the isopropyl alcohol and unreacted monomers were recovered under reduced pressure while being heated to 60°C, thereby obtaining an acrylic resin (B-1) dispersed in pure water.
[0271] Binder resin (B-2): acrylic resin (containing hydroxyl and carboxyl groups)
[0272] Acrylic resin (B-2) was obtained in the same manner as binder resin (B-1), except that methyl methacrylate (α), ethyl acrylate (β), 2-hydroxyethyl acrylate (γ), and acrylonitrile (δ) / acrylic acid (ε) were added to the starting materials added to the stainless steel reaction container at a ratio of (α) / (β) / (γ) / (δ) / (ε)=55 / 32 / 6 / 2 / 5 (mass ratio) to make the total 100 parts by mass.
[0273] Binder resin (B-3): polyester resin
[0274] A thermosetting polyester resin aqueous dispersion (Z-836, manufactured by Huying Chemical Industry Co., Ltd., solid content concentration: 15% by weight) was used.
[0275] <Crosslinking agent (C)>
[0276] Cross-linking agent (C-1): melamine resin (hydroxymethylated melamine)
[0277] "Nikalak" (registered trademark) MW-035 (solid content concentration: 70 mass %, solvent: water) manufactured by Sanwa Chemical Co., Ltd. was used.
[0278] Cross-linking agent (C-2): Carbodiimide compound
[0279] “Carbohydrate Line” (registered trademark) V-04 (solid content concentration: 40% by mass, solvent: water) manufactured by Nisshinbo Chemical Co., Ltd. was used.
[0280] <Antistatic agent (D)>
[0281] Antistatic agent (D-1): CNT aqueous dispersion 1
[0282] 1.0 mg of linear two-layer CNTs (manufactured by Science Labrators Co., Ltd., with a diameter of 5 nm and an aspect ratio of 3000) as CNTs, 3.0 mg of sodium carboxymethyl cellulose (Sigma-Aldrich Japan Co., Ltd.) (hereinafter referred to as CMC-Na) as a CNT dispersant, and 666 mg of water were added to a sample tube to prepare a CNT aqueous dispersion. The mixture was irradiated with ultrasound for 30 minutes using an ultrasonic crusher (VCX-502 manufactured by Tokyo Rikakiki Co., Ltd., with an output of 250 W and direct irradiation), thereby obtaining a uniform CNT aqueous dispersion (D-1) composed of CNTs and CNT dispersant (CNT concentration 0.15 wt%, CNT dispersant 0.45 wt%, CNT dispersant / CNT = 3.0).
[0283] Antistatic agent (D-2): polythiophene compound
[0284] To 1887 parts by mass of an aqueous solution containing 20.8 parts by mass of polystyrene sulfonic acid as an acidic polymer compound, 49 parts by mass of a 1% by mass aqueous solution of iron (III) sulfate, 8.8 parts by mass of 3,4-ethylenedioxythiophene as a thiophene compound, and 117 parts by mass of a 10.9% by mass aqueous solution of peroxodisulfuric acid were added. The mixture was stirred at 18° C. for 23 hours, and 154 parts by mass of a cation exchange resin (“Lebatit” (registered trademark) Monoplastic S100H; manufactured by Lanxess Co., Ltd.) and 232 parts by mass of an anion exchange resin (“Lebatit” (registered trademark) Monoplastic M800; manufactured by Lanxess Co., Ltd.) were added to the mixture. After stirring for 2 hours, the ion exchange resin was filtered and separated to obtain an antistatic agent (D-2) (solid content concentration of 1.3% by weight) which was a mixture of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid.
[0285] Antistatic agent (D-3): CNT aqueous dispersion 2
[0286] The CNT aqueous dispersion 2 was prepared as follows.
[0287] First, 1.0 mg of CNT (2-layer CNT: manufactured by Science Lab Ltd., with an average diameter of 5 nm), 1.0 mg of CMC-Na as a CNT dispersant, and 248 mg of water were added to a 50 mL sample tube to prepare a CNT aqueous dispersion. The mixture was irradiated with ultrasound for 30 minutes using an ultrasonic crusher (VCX-502 manufactured by Tokyo Rikakiki Co., Ltd., with an output of 250 W, direct irradiation), thereby obtaining a uniform CNT aqueous dispersion (CNT concentration 0.40 wt%, CNT dispersant 0.40 wt%, (B) / (A) = 0.5).
[0288] Antistatic agent (D-4): Carbon nanofiber
[0289] Carbon nanofibers having an average diameter of 15 nm and an average length of 1 μm (manufactured by DEMCO Co., Ltd., trade name “CNF-T”, tubular, 3% by mass cyclohexanone dispersed type) were used.
[0290] <Cross-linking catalyst>
[0291] Catalyst 1: Dodecylbenzenesulfonic acid
[0292] “NACURE” (registered trademark) 5528 (manufacturer: KING INDUSTRIES, NACURE DDBSA series: dodecylbenzenesulfonic acid catalyst (blocked acid catalyst)) manufactured by Kusumoto Chemicals Co., Ltd. was used.
[0293] Catalyst 2: Platinum catalyst
[0294] A platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "CAT-PL-50T") was used.
[0295] (Example 1)
[0296] Resin composition for forming the resin layer:
[0297] The release agent (A-1), the binder resin (B-1), and the crosslinking agent (C-1) were mixed in a solid content mass ratio of (A-1) / (B-1) / (C-1)=25 / 30 / 45. Next, an antistatic agent (D-1) was added in a solid content of 100 parts by mass of the total of the release agent (A-1), the binder resin (B-1), and the crosslinking agent (C-1), and 5 parts by mass of the catalyst 1 were added, and the solid content concentration was adjusted by adding water according to the coating method and the target thickness described later. In order to further improve the coating property on the polyester film, an acetylene glycol surfactant ("Olfin" (registered trademark) EXP.4200 manufactured by Nissin Chemical Industry Co., Ltd.) was added in an amount of 0.1 parts by mass relative to 100 parts by mass of the total mixed resin composition.
[0298] Polyester film:
[0299] PET particles (intrinsic viscosity 0.64 dl / g) containing two kinds of particles (4 parts by mass of silica particles with a primary particle size of 0.3 μm and 2 parts by mass of calcium carbonate particles with a primary particle size of 0.8 μm) were fully vacuum dried, supplied to an extruder to be melted at 280°C, extruded from a T-shaped die in a sheet form, and wound on a mirror casting drum with a surface temperature of 25°C using an electrostatic casting method to cool and solidify it, thereby obtaining an unstretched film (film A). The unstretched film was heated to 90°C and stretched 3.1 times in the longitudinal direction to prepare a uniaxially stretched film (film B).
[0300] Laminated film
[0301] After the uniaxially stretched film was subjected to corona discharge treatment in air, the resin composition prepared by the method described in the item of the resin composition for forming the resin layer was applied with a wire bar coater at a coating thickness of about 6 μm. Then, the two ends of the uniaxially stretched film coated with the resin composition in the width direction were held by clamps and guided to a tenter, and the solvent of the resin composition was dried in a preheating area with an atmospheric temperature of 90 to 100°C. Then, it was continuously stretched 3.6 times in the width direction in a stretching area at 100°C, and then a heat treatment was performed for 20 seconds in a heat treatment area at 230°C to form a resin layer X, and a 5% relaxation treatment was further performed in the width direction at the same temperature to obtain a laminated film in which the crystal orientation of the polyester film was completed. The properties of the obtained laminated film are shown in Tables 3 and 4.
[0302] (Examples 2 to 7, Comparative Examples 1 to 3)
[0303] A laminated film was obtained by the same method as in Example 1 except that the composition of the resin composition was changed as shown in Table 1. Tables 3 and 4 show the properties and the like of the obtained laminated film.
[0304] (Example 8)
[0305] Using the resin composition of Example 1, a laminated film was obtained by the following method. As a substrate, a PET film "LumiLa" (registered trademark) T60 (substrate thickness 50 μm) manufactured by Toray Co., Ltd. was used. The resin composition was applied to the substrate using a wire rod. Then, in order to prevent deformation caused by heat, a SUS plate film of the same type as the film was configured, and after the four sides were gripped with binder clips without gaps, a hot air furnace was used to dry / cured at 230°C for 2 minutes to obtain a laminated film. The properties of the obtained laminated film are shown in Tables 3 and 4.
[0306] (Comparative Example 4)
[0307] A laminated film was produced as follows.
[0308] First, binder resin (B-3) was added to antistatic agent (D-3), mixed and stirred for 15 minutes at 500 rpm by electromagnetic stirrer to obtain CNT dispersion. The composition weight ratio of antistatic agent (D-3), CNT dispersant, and binder resin (B-3) in the CNT dispersion (the total weight of (D-3), CNT dispersant, and (B-3) was set to 100 weight %) is as follows.
[0309] (D-3) 4.0 wt%
[0310] CNT dispersant 2.0 wt%
[0311] (B-3) 94.0 wt%
[0312] At this time, the weight ratio of CNT dispersant / (D-3) was 0.5.
[0313] Next, an acrylic resin (A-4) containing a long-chain alkyl group prepared by the following copolymerization composition and the above-mentioned CNT dispersion liquid are mixed in a manner such that [the total weight of (D-3), the CNT dispersant and (B-3)] / [the weight of (A-4)]=100 parts by weight / 10 parts by weight to prepare a coating resin composition.
[0314] Next, PET pellets (intrinsic viscosity 0.63 dl / g) containing substantially no particles were fully vacuum dried, supplied to an extruder, melted at 285°C, extruded from a T-shaped die in a sheet form, and wound on a mirror casting drum with a surface temperature of 25°C using an electrostatic casting method to cool and solidify. The unstretched film was heated to 90°C and stretched 3.4 times in the longitudinal direction to prepare a uniaxially stretched film (B film). The film was subjected to a corona discharge treatment in air.
[0315] Next, the coating resin composition was applied to the corona discharge treated surface of the uniaxially stretched film using a rod coater. The two ends of the uniaxially stretched film coated with the coating resin composition were held by a clamp in the width direction and led to the preheating area. After the atmosphere temperature was set to 75°C, the atmosphere temperature was then set to 110°C using a radiation heater, and then the atmosphere temperature was set to 90°C to dry the coating resin composition. Then, it was continuously stretched 3.5 times in the width direction in a heating area (stretching area) at 120°C, and then heat treated for 20 seconds in a heat treatment area (heat setting area) at 230°C to obtain a laminated film with completed crystal orientation.
[0316] (Comparative Example 5)
[0317] A laminated film was produced as follows. 100 parts by mass of a silicone release agent (A-5) and 1 part by mass of a catalyst 2 (platinum catalyst) were diluted with toluene to obtain a solution having a solid content concentration of 1.5% by mass. An antistatic agent (D-4) was added to the solution in such a manner that the content of the antistatic release agent layer was 5% by mass to prepare a coating liquid. Next, the coating liquid was evenly coated on a polyethylene terephthalate (PET) film [manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., trade name "T-100"] having a thickness of 38 μm using a Meyer rod in such a manner that the thickness after drying was 0.1 μm. Next, the resin layer was formed by heating in a dryer at 130°C for 1 minute to produce a laminated film.
[0318] (Examples 9, 10, Comparative Example 6)
[0319] The resin compositions listed in Tables 1 and 2 were applied to each surface using a wire bar coater at a coating thickness of about 6 μm. Specifically, the surface of the uniaxially stretched film substrate film opposite to the resin layer X was also subjected to a corona discharge treatment in air, and the resin composition for forming the resin layer Y listed in Table 2 was applied using a wire bar coater at a coating thickness of about 6 μm, and the resin layer Y was formed simultaneously with the resin layer X by the same drying / stretching / heat treatment as the above-mentioned resin layer X. A laminated film was obtained by the same method as in Example 1. The properties of the obtained laminated film are shown in Tables 3 and 4.
[0320] (Examples 11 and 12)
[0321] As the raw material of the polyester film, PET pellets (Example 11) containing recycled raw materials and biomass raw materials (Example 12) in the proportions shown in Table 1 were used, and a laminated film was obtained by the same method as in Example 3. The properties of the obtained laminated film are shown in Tables 2 and 3. It should be noted that the so-called recycled raw materials here are the uncoated parts removed in the film-making process of the polyester film in Examples 1 to 10, which were cut into small pieces and kneaded with the original raw materials when the polyester film was made. On the other hand, the biomass raw material is PET with a biomass degree of 15% and a part of the ethylene glycol unit derived from plants.
[0322] (Example 13)
[0323] A laminated film was obtained by the same method as in Example 10 except that PET pellets containing recycled raw materials in the ratios shown in Table 1 were used in the same manner as in Example 11 as the raw material of the polyester film.
[0324] [Table 1]
[0325]
[0326] [Table 2]
[0327]
[0328] [Table 3]
[0329]
[0330] [Table 4]
[0331] Table 4
[0332]
[0333] Industrial Availability
[0334] The laminated film of the present invention has both the light peelability and antistatic properties of the resin layer, so it has excellent processability in the process of peeling the surface layer, and there is no contamination caused by silicone and no shedding of antistatic agents. Therefore, it can be suitably used as a process film for the manufacturing process of electronic components such as laminated ceramic capacitors and inductors, and a process film for the manufacturing process of batteries such as lithium-ion batteries and all-solid-state batteries.
Claims
1. A laminated film having a resin layer X containing an antistatic agent on at least one surface of a thermoplastic resin substrate film, which satisfies all of the following conditions (1) to (3), (1) The average content ratio of nitrogen atoms to carbon atoms per 1 nm of the resin layer X calculated from the ratio of nitrogen to carbon elements (N / C) and the thickness of the resin layer X is 0.0030 nm. -1 In the above, the ratio of nitrogen to carbon is calculated by high-resolution Rutherford backscattering method (HR-RBS method), and the unit of thickness is nm. (2) The surface resistivity of the resin layer X is 1.0×10 10 Ω / □ or less, (3) The surface free energy of the resin layer X is 20.0 mN / m or more and less than 30.0 mN / m.
2. A laminated film comprising a thermoplastic resin base film and a resin layer X containing an antistatic agent on at least one surface thereof, wherein the resin layer X contains a long-chain alkyl resin, a melamine compound and an acrylic resin. 3 . The laminated film according to claim 1 , wherein the antistatic agent contained in the resin layer X is a conductive carbon material. The laminated film according to claim 3 , wherein the antistatic agent contained in the resin layer X is carbon nanotubes.
5. The laminate film according to any one of claims 1 to 4, wherein when the surface of the resin layer X is analyzed by time-of-flight secondary ion mass spectrometry, the ratio of the peak intensity P of the fragment derived from polydimethylsiloxane to the peak intensity K of the fragment detected with maximum intensity, i.e. P / K[-], is less than 0.
01.
6. The laminated film according to any one of claims 1 to 5, wherein the resin layer X contains a long-chain alkyl resin as a release agent, and the long-chain alkyl resin has an exothermic peak temperature Tc of 30°C to 90°C during a cooling process when the temperature is increased from 25°C to 200°C at 20°C / min and then decreased from 200°C to -50°C at 20°C / min using a differential scanning calorimeter DSC. 7 . The laminated film according to claim 6 , wherein the resin layer X contains a long-chain alkyl resin and a melamine compound, and contains at least one resin selected from the group consisting of acrylic resins, epoxy resins, and urethane resins.
8. According to any one of claims 1 to 7, for the X-ray absorption fine structure XAFS spectrum of the resin layer X measured by the partial electron yield method, and the X-ray absorption near-edge structure XANES spectrum of the K absorption edge of carbon, when the angle between the incident X-ray and the resin layer surface is set to θ and the spectrum intensity of 293.5 eV is set to I(θ), I(15°)-I(90°)≥0.10 is satisfied. 9 . The laminated film according to claim 2 , wherein the long-chain alkyl resin is a block copolymer. 10 . The laminated film according to claim 1 , wherein the thermoplastic resin substrate film is a polyester film containing at least one of a biomass raw material and a recycled raw material.
11. The laminated film according to any one of claims 1 to 10, comprising a resin layer Y on the surface opposite to the resin layer X, wherein the surface resistivity value of any surface is 1.0×10 10 Ω / □ or less. 12 . The laminated film according to claim 11 , wherein the resin layer Y contains carbon nanotubes. 13 . The laminated film according to claim 1 , which is used in a process for producing an electronic component or a battery component.
Citation Information
Patent Citations
Permanentantistatic primer layer
EP0602713A1
Laminate
JP2000006324A
Release film, resin sheet molding carrier film and resin sheet protecting film using the same
JP2000158611A
Peel film and its manufacturing method
JP2007190717A
Antistatic film for polarizing plate protection
JP2010072423A